1st international summer school for neuropathology and epilepsy surgery (INES 2013), held in Erlangen, Germany, September 16th-20th, 2013 - Blümcke, Ingmar; Coras, Roland (Brain Pathology, 2014)
CRIS-Team Scopus Importer:2022-08-05

7T MRI features in control human hippocampus and hippocampal sclerosis: An ex vivo study with histologic correlations - Coras, Roland; Milesi, Gloria; Zucca, Ileana; Mastropietro, Alfonso; Scotti, Alessandro; Figini, Matteo; Muehlebner, Angelika; Heß, Andreas; Graf, Wolfgang; Tringali, Giovanni; Blümcke, Ingmar; Villani, Flavio; et al. (Epilepsia, 2014)
Hippocampal sclerosis (HS) is the major structural brain lesion in patients with temporal lobe epilepsy (TLE). However, its internal anatomic structure remains difficult to recognize at 1.5 or 3 Tesla (T) magnetic resonance imaging (MRI), which allows neither identification of specific pathology patterns nor their proposed value to predict postsurgical outcome, cognitive impairment, or underlying etiologies. We aimed to identify specific HS subtypes in resected surgical TLE samples on 7T MRI by juxtaposition with corresponding histologic sections.Fifteen nonsclerotic and 18 sclerotic hippocampi were studied ex vivo using an experimental 7T MRI scanner. T2 -weighted images (T2wi) and diffusion tensor imaging (DTI) data were acquired and validated using a systematic histologic analysis of same specimens along the anterior-posterior axis of the hippocampus.In nonsclerotic hippocampi, differences in MR intensity could be assigned to seven clearly recognizable layers and anatomic boundaries as confirmed by histology. All hippocampal subfields could be visualized also in the hippocampal head with three-dimensional imaging and angulated coronal planes. Only four discernible layers were identified in specimens with histopathologically confirmed HS. All sclerotic hippocampi showed a significant atrophy and increased signal intensity along the pyramidal cell layer. Changes in DTI parameters such as an increased mean diffusivity, allowed to distinguish International League Against Epilepsy (ILAE) HS type 1 from type 2. Whereas the increase in T2wi signal intensities could not be attributed to a distinct specific histopathologic substrate, that is, decreased neuronal or increased glial cell densities, intrahippocampal projections and fiber tracts were distorted in HS specimens suggesting a complex disorganization of the cellular composition, fiber networks, as well as its extracellular matrix.Our data further advocate high-resolution MRI as a helpful and promising diagnostic tool for the investigation of hippocampal pathology along the anterior-posterior extent in TLE, as well as in other neurologic and neurodegenerative disorder
EVALuna2:7255

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

A deep learning-based histopathology classifier for Focal Cortical Dysplasia - Vorndran, Jörg; Neuner, Christoph; Coras, Roland; Hoffmann, Lucas; Geffers, Simon; Honke, Jonas; Herms, Jochen; Roeber, Sigrun; Hamer, Hajo; Brandner, Sebastian; Hartlieb, Till; Pieper, Tom; et al. (Neural Computing & Applications, 2023)
A light microscopy-based histopathology diagnosis of human brain specimens obtained from epilepsy surgery remains the gold standard to confirm the underlying cause of a patient’s focal epilepsy and further inform postsurgical patient management. The differential diagnosis of neocortical specimens in the realm of epilepsy surgery remains, however, challenging. Herein, we developed an open access, deep learning-based classifier to histopathologically assess whole slide microscopy images (WSI) and to automatically recognize various subtypes of Focal Cortical Dysplasia (FCD), according to the ILAE consensus classification update of 2022. We trained a convolutional neuronal network (CNN) with fully digitalized WSI of hematoxylin–eosin stainings obtained from 125 patients covering the spectrum of mild malformation of cortical development (mMCD), mMCD with oligodendroglial hyperplasia in epilepsy (MOGHE), FCD ILAE Type 1a, 2a and 2b using 414 formalin-fixed and paraffin-embedded archival tissue blocks. An additional series of 198 postmortem tissue blocks from 59 patients without neurological disorders served as control to train the CNN for homotypic frontal, temporal and occipital areas and heterotypic Brodmann areas 4 and 17, entorhinal cortex and dentate gyrus. Special stains and immunohistochemical reactions were used to comprehensively annotate the region of interest. We then programmed a novel tile extraction pipeline and graphical dashboard to visualize all areas on the WSI recognized by the CNN. Our deep learning-based classifier is able to compute 1000 × 1000 µm large tiles and recognizes 25 anatomical regions and FCD categories with an accuracy of 98.8% (F1 score = 0.82). Microscopic review of regions predicted by the network confirmed these results. This deep learning-based classifier will be made available as online web application to support the differential histopathology diagnosis in neocortical human brain specimens obtained from epilepsy surgery. It will also serve as blueprint to build a digital histopathology slide suite addressing all major brain diseases encountered in patients with surgically amenable focal epilepsy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Classification; Convolutional neuronal network; Cortex; Deep learning; Digital pathology; Epilepsy; FCD1; FCD2; mMCD; MOGHE

Advantages of magnetoencephalography, neuronavigation and intraoperative MRI in epilepsy surgery re-operations - Shawarba, Julia; Kaspar, Burkhard; Rampp, Stefan; Winter, Fabian; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2021)
Objective: Management of patients after failed epilepsy surgery is still challenging. Advanced diagnostic and intraoperative tools including magneto-encephalography (MEG) as well as neuronavigation and intraoperative magnetic resonance imaging (iopMRI) may contribute to a better postoperative seizure outcome in this patient group. Methods: We retrospectively analyzed consecutive patients after reoperation of failed epilepsy surgery for medically refractory epilepsy at the University of Erlangen between 1988 and 2017. Inclusion criteria for patients were available MEG, neuronavigation and iopMRI data. The Engel scale was used to categorize seizure outcome. Results: We report on 27 consecutive patients (13 female/14 male mean age at first surgery 29.4 years) who had operative revision of the first resection after failed epilepsy surgery. An improved seizure outcome postoperatively was observed in 78% of patients (p < 0.001) with 55% seizure free (Engel I) patients after a mean follow-up time of 4.9 years. In detail, 80% of lesional cases were seizure free compared to 59% of MRI negative patients. Localizing MEG spike activity in the vicinity of the first resection cavity was present in 12 of 27 patients (44%) corresponding to 83% (10/12) of MEG localizing spike patients having advanced seizure outcome after operative revision. Conclusion: Re-operation after failed surgery in refractory epilepsy may lead to a better seizure outcome in the majority of patients. Preoperative MEG may support the decision for surgery and may facilitate targeting epileptogenic tissue for re-resection by employing navigation and iopMR imaging.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Failed epilepsy surgery; intraoperative MR imaging; MEG; neuronavigation; reoperation; seizure outcome

Age-dependent increase of perineuronal nets in the human hippocampus and precocious aging in epilepsy - Lehner, Annika; Hoffmann, Lucas; Rampp, Stefan; Coras, Roland; Paulsen, Friedrich; Frischknecht, Renato; Hamer, Hajo; Walther, Katrin; Brandner, Sebastian; Hofer, Wiebke; Pieper, Tom; Reisch, Lea Marie; et al. (Epilepsia Open, 2024)
Objective: Perineuronal nets (PNN) are specialized extracellular matrix (ECM) components of the central nervous system, frequently accumulating at the surface of inhibitory GABAergic interneurons. While an altered distribution of PNN has been observed in neurological disorders including Alzheimer's disease, schizophrenia and epilepsy, their anatomical distribution also changes during physiological brain maturation and aging. Such an age-dependent shift was experimentally associated also with hippocampal engram formation during brain maturation. Our aim was to histopathologically assess PNN in the hippocampus of adult and pediatric patients with temporal lobe epilepsy (TLE) compared to age-matched post-mortem control subjects and to compare PNN-related changes with memory impairment observed in our patient cohort. Methods: Sixty-six formalin-fixed and paraffin-embedded tissue specimens of the human hippocampus were retrieved from the European Epilepsy Brain Bank. Twenty-nine patients had histopathologically confirmed hippocampal sclerosis (HS), and eleven patients suffered from TLE without HS. PNN were immunohistochemically visualized using an antibody directed against aggrecan and manually counted from hippocampus subfields and the subiculum. Results: PNN density increased with age in both human controls and TLE patients. However, their density was significantly higher in all HS patients compared to age-matched controls. Intriguingly, TLE patients presented presurgically with better memory when their hippocampal PNN density was higher (p < 0.05). Significance: Our results were compatible with age-dependent ECM specialization in the human hippocampus and its precocious aging in the epileptic condition. These observations confirm recent experimental animal models and also support the notion that PNN play a role in memory formation in the human brain. Plain Language Summary: “Perineuronal nets” (PNN) are a specialized compartment of the extracellular matrix (ECM), especially surrounding highly active neurons of the mammalian brain. There is evidence that PNN play a role in memory formation, brain maturation, and in some pathologies like Alzheimer's disease, schizophrenia or epilepsy. In this study, we investigated the role of PNN in patients suffering from drug-resistant focal epilepsy compared to controls. We found that with increasing age, more neurons are surrounded by PNN. Similarly, all epilepsy patients but especially patients with better memory performance also had more PNN. This study raises further interest in studying ECM molecules in the human brain under physiological and pathophysiological conditions.
CRIS-Team Scopus Importer:2024-06-21
Keywords: brain; extracellular matrix; hippocampal sclerosis; maturation; neuropathology

A glutaminyl cyclase-catalyzed α-synuclein modification identified in human synucleinopathies - Hartlage-Rübsamen, Maike; Bluhm, Alexandra; Moceri, Sandra; Machner, Lisa; Köppen, Janett; Schenk, Mathias; Hilbrich, Isabel; Holzer, Max; Weidenfeller, Martin; Richter, Franziska; Coras, Roland; Serrano, Geidy E.; et al. (Acta Neuropathologica, 2021)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that is neuropathologically characterized by degeneration of dopaminergic neurons of the substantia nigra (SN) and formation of Lewy bodies and Lewy neurites composed of aggregated α-synuclein. Proteolysis of α-synuclein by matrix metalloproteinases was shown to facilitate its aggregation and to affect cell viability. One of the proteolysed fragments, Gln79-α-synuclein, possesses a glutamine residue at its N-terminus. We argue that glutaminyl cyclase (QC) may catalyze the pyroglutamate (pGlu)79-α-synuclein formation and, thereby, contribute to enhanced aggregation and compromised degradation of α-synuclein in human synucleinopathies. Here, the kinetic characteristics of Gln79-α-synuclein conversion into the pGlu-form by QC are shown using enzymatic assays and mass spectrometry. Thioflavin T assays and electron microscopy demonstrated a decreased potential of pGlu79-α-synuclein to form fibrils. However, size exclusion chromatography and cell viability assays revealed an increased propensity of pGlu79-α-synuclein to form oligomeric aggregates with high neurotoxicity. In brains of wild-type mice, QC and α-synuclein were co-expressed by dopaminergic SN neurons. Using a specific antibody against the pGlu-modified neo-epitope of α-synuclein, pGlu79-α-synuclein aggregates were detected in association with QC in brains of two transgenic mouse lines with human α-synuclein overexpression. In human brain samples of PD and dementia with Lewy body subjects, pGlu79-α-synuclein was shown to be present in SN neurons, in a number of Lewy bodies and in dystrophic neurites. Importantly, there was a spatial co-occurrence of pGlu79-α-synuclein with the enzyme QC in the human SN complex and a defined association of QC with neuropathological structures. We conclude that QC catalyzes the formation of oligomer-prone pGlu79-α-synuclein in human synucleinopathies, which may—in analogy to pGlu-Aβ peptides in Alzheimer’s disease—act as a seed for pathogenic protein aggregation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Animal models; Dementia with Lewy bodies; Glutaminyl cyclase; Parkinson’s disease; Post-translational modification; Substantia nigra; α-Synuclein

Alzheimer's disease protease-containing plasma extracellular vesicles transfer to the hippocampus via the choroid plexus - Lee, Jung Hyun; Ostalecki, Christian; Oberstein, Timo; Schierer, Stefan; Zinser, Elisabeth; Eberhardt, Martin; Blume, Katja; Plosnita, Bianca; Stich, Lena; Bruns, Heiko; Coras, Roland; Vera González, Julio; et al. (EBioMedicine, 2022)
Background: Plasma extracellular vesicles (pEV) can harbor a diverse array of factors including active proteases and the amyloid-precursor-protein (APP) cleavage product Aβ, involved in plaque formation in Alzheimer`s diseases (AD). A potential role of such vesicles in AD pathology is unexplored. Methods: In a case-control study of randomly selected patients with AD and other neurological diseases (n = 14), and healthy controls (n = 7), we systematically analyzed the content of pEV, using different assay systems. In addition, we determined their entry path into brain tissue, employing animal (mice) injection experiments with ex vivo generated EV that were similar to AD-pEV, followed by multi antigen analysis (MAA) of brain tissue (n = 4 per condition). The results were compared with an IHC staining of human brain tissue in a small cohort of AD patients (n = 3) and controls with no neurodegenerative diseases (n = 3). Findings: We show that pEV levels are considerably upregulated in AD patients. Besides numerous inflammatory effectors, AD-pEV contained α-, β- and γ-secretases, able to cleave APP in in target cells. In vitro generated EV with similar characteristics as AD-pEV accumulated in the choroid plexus (CP) of injected animals and reached primarily hippocampal neurons. Corroborating findings were made in human brain samples. An inhibitor of hyaluronic-acid-synthetase (HAS) blocked uploading of proteases and Hyaluronan onto EV in vitro and abolished CP targeting in animal injection experiments. Interpretation: We conclude that protease-containing pEV could be part of a communication axis between the periphery and the brain that could be become detrimental depending on pEV concentration and duration of target cell impact.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Alzheimer's disease; APP; Aβ; BACE; Choroid plexus; Hippocampus; Hyaluronan; Hyaluronic acid synthetase; Plasma extracellular vesicles; Secretases

Analysis of 1386 epileptogenic brain lesions reveals association with DYRK1A and EGFR - Boßelmann, Christian M.; Leu, Costin; Brünger, Tobias; Hoffmann, Lucas; Baldassari, Sara; Chipaux, Mathilde; Coras, Roland; Kobow, Katja; Hamer, Hajo; Delev, Daniel; Rössler, Karl; Bien, Christian G.; et al. (Nature Communications, 2024)
Lesional focal epilepsy (LFE) is a common and severe seizure disorder caused by epileptogenic lesions, including malformations of cortical development (MCD) and low-grade epilepsy-associated tumors (LEAT). Understanding the genetic etiology of these lesions can inform medical and surgical treatment. We conducted a somatic variant enrichment mega-analysis in brain tissue from 1386 individuals who underwent epilepsy surgery, including 599 previously unpublished individuals with ultra-deep ( > 1600x) targeted panel sequencing. Here we confirm four known associations (BRAF, SLC35A2, MTOR, PTPN11), support eight associations without prior statistical support (FGFR1, PIK3CA, AKT3, NF1, PTEN, RHEB, KRAS, NRAS), and identify novel associations for two genes, DYRK1A and EGFR. Both novel genes show specific histopathological phenotypes, interact with LFE genes and pathways, and may represent promising candidates as biomarkers and potentially druggable target

Anaplastic ganglioglioma-A diagnosis comprising several distinct tumour types - Reinhardt, Annekathrin; Pfister, Kristin; Schrimpf, Daniel; Stichel, Damian; Sahm, Felix; Reuss, David E.; Capper, David; Wefers, Annika K.; Ebrahimi, Azadeh; Sill, Martin; Felsberg, Joerg; Reifenberger, Guido; et al. (Neuropathology and Applied Neurobiology, 2022)
Aims Anaplastic ganglioglioma is a rare tumour, and diagnosis has been based on histological criteria. The 5th edition of the World Health Organization Classification of Tumours of the Central Nervous System (CNS WHO) does not list anaplastic ganglioglioma as a distinct diagnosis due to lack of molecular data in previous publications. We retrospectively compiled a cohort of 54 histologically diagnosed anaplastic gangliogliomas to explore whether the molecular profiles of these tumours represent a separate type or resolve into other entities. Methods Samples were subjected to histological review, desoxyribonucleic acid (DNA) methylation profiling and next-generation sequencing. Morphological and molecular data were summarised to an integrated diagnosis. Results The majority of tumours designated as anaplastic gangliogliomas resolved into other CNS WHO diagnoses, most commonly pleomorphic xanthoastrocytoma (16/54), glioblastoma, isocitrate dehydrogenase protein (IDH) wild type and diffuse paediatric-type high-grade glioma, H3 wild type and IDH wild type (11 and 2/54), followed by low-grade glial or glioneuronal tumours including pilocytic astrocytoma, dysembryoplastic neuroepithelial tumour and diffuse leptomeningeal glioneuronal tumour (5/54), IDH mutant astrocytoma (4/54) and others (6/54). A subset of tumours (10/54) was not assignable to a CNS WHO diagnosis, and common molecular profiles pointing to a separate entity were not evident. Conclusions In summary, we show that tumours histologically diagnosed as anaplastic ganglioglioma comprise a wide spectrum of CNS WHO tumour types with different prognostic and therapeutic implications. We therefore suggest assigning this designation with caution and recommend comprehensive molecular workup.
CRIS-Team WoS Importer:2022-09-23

Anatomy-guided resections for paralimbic tumors in the temporo-insular region: combining tumor and epilepsy surgery concepts - Alkassm, Emad; Grote, Alexander; Berger, Björn; Woermann, Friedrich G.; Ersoy, Tunc Faik; Coras, Roland; Kalbhenn, Thilo; Simon, Matthias (Frontiers in Neurology, 2024)
Object: Tumors in the temporo-mesial region often extend into the insula and vice versa. The present study investigated the results of a surgical strategy that combines principles of tumor and epilepsy surgery. Methods: We retrospectively analyzed 157 consecutive patients with intrinsic brain tumors in the temporo-mesial region, with varying degrees of extensions into the insula (44 patients, 28.0%). The surgical strategy utilized “anatomy-guided resection,” targeting specific anatomical compartments infiltrated by the tumor (e.g., temporal pole, anterior temporo-mesial region = uncus and hippocampal head, posterior temporo-mesial, insula) rather than treating the tumor as a single mass. Results: The most frequent histologies were ganglioglioma CNS WHO grade 1 (55 patients, 35.0%) and IDH1 wildtype glioblastoma (36 patients, 22.9%). Tumor infiltration was most commonly found in the anterior temporo-mesial compartment (145 patients, 92.4%). An anterior temporal lobectomy was part of the surgical strategy in 131 cases (83.4%). Seventy-six patients (48.4%) with drug-resistant epilepsy underwent a formal presurgical epilepsy work-up, including depth electrode placement in three cases. Complete resections were achieved in 117 patients (74.5%), with supramarginal resections performed in 89 cases (56.7%). Four patients experienced non-temporary neurological complications (CTCAE grade 3–5). At 6 months, 127 of 147 assessable patients (86.4%) were free from seizures or auras (ILAE class 1), excluding early postoperative seizures (<30 days). At 24 months, 122 of 144 assessable cases (84.7%) remained seizure-free (ILAE class 1). Kaplan–Meier estimates for 5-year overall survival were 98.5% for non-recurrent glioneuronal tumors. The 2-year overall survival estimates were 96.0% for 24 primary diffuse CNS WHO grade 2 and 3 gliomas and 55.2% for 30 patients undergoing first surgeries for glioblastomas/astrocytomas CNS WHO grade 4. Conclusion: Combining both epilepsy and tumor surgery concepts in the surgical treatment of intrinsic brain tumors involving the mesial temporal lobe, often extending into the insula, led to more extensive resections, improved seizure outcomes, and potentially even better patient survival outcomes.
CRIS-Team Scopus Importer:2024-11-22
Keywords: epilepsy surgery; insula; paralimbic; supramarginal resection; temporo-mesial

A self-supervised multimodal deep learning approach to differentiate post-radiotherapy progression from pseudoprogression in glioblastoma - Gomaa, Ahmed; Huang, Yixing; Stephan, Pluvio; Breininger, Katharina; Frey, Benjamin; Dörfler, Arnd; Schnell, Oliver; Delev, Daniel; Coras, Roland; Donaubauer, Anna-Jasmina; Schmitter, Charlotte; Stritzelberger, Jenny; et al. (Scientific Reports, 2025)
Accurate differentiation of pseudoprogression (PsP) from True Progression (TP) following radiotherapy (RT) in glioblastoma patients is crucial for optimal treatment planning. However, this task remains challenging due to the overlapping imaging characteristics of PsP and TP. This study therefore proposes a multimodal deep-learning approach utilizing complementary information from routine anatomical MR images, clinical parameters, and RT treatment planning information for improved predictive accuracy. The approach utilizes a self-supervised Vision Transformer (ViT) to encode multi-sequence MR brain volumes to effectively capture both global and local context from the high dimensional input. The encoder is trained in a self-supervised upstream task on unlabeled glioma MRI datasets from the open BraTS2021, UPenn-GBM, and UCSF-PDGM datasets (n = 2317 MRI studies) to generate compact, clinically relevant representations from FLAIR and T1 post-contrast sequences. These encoded MR inputs are then integrated with clinical data and RT treatment planning information through guided cross-modal attention, improving progression classification accuracy. This work was developed using two datasets from different centers: the Burdenko Glioblastoma Progression Dataset (n = 59) for training and validation, and the GlioCMV progression dataset from the University Hospital Erlangen (UKER) (n = 20) for testing. The proposed method achieved competitive performance, with an AUC of 75.3%, outperforming the current state-of-the-art data-driven approaches. Importantly, the proposed approach relies solely on readily available anatomical MRI sequences, clinical data, and RT treatment planning information, enhancing its clinical feasibility. The proposed approach addresses the challenge of limited data availability for PsP and TP differentiation and could allow for improved clinical decision-making and optimized treatment plans for glioblastoma patients.
CRIS-Team Scopus Importer:2025-05-30

A Whole-Slide Image Managing Library Based on Fastai for Deep Learning in the Context of Histopathology: Two Use-Cases Explained - Neuner, Christoph; Coras, Roland; Blümcke, Ingmar; Popp, Alexander; Schlaffer, Sven-Martin; Wirries, Andre; Buchfelder, Michael; Jabari, Samir (Applied Sciences, 2022)
Background: Processing whole-slide images (WSI) to train neural networks can be intricate and labor intensive. We developed an open-source library dealing with recurrent tasks in the processing of WSI and helping with the training and evaluation of neuronal networks for classification tasks. Methods: Two histopathology use-cases were selected and only hematoxylin and eosin (H&E) stained slides were used. The first use case was a two-class classification problem. We trained a convolutional neuronal network (CNN) to distinguish between dysembryoplastic neuroepithelial tumor (DNET) and ganglioglioma (GG), two neuropathological low-grade epilepsy-associated tumor entities. Within the second use case, we included four clinicopathological disease conditions in a multilabel approach. Here we trained a CNN to predict the hormone expression profile of pituitary adenomas. In the same approach, we also predicted clinically silent corticotroph adenoma. Results: Our DNET-GG classifier achieved an AUC of 1.00 for the ROC curve. For the second use case, the best performing CNN achieved an area under the curve (AUC) of 0.97 for the receiver operating characteristic (ROC) for corticotroph adenoma, 0.86 for silent corticotroph adenoma, and 0.98 for gonadotroph adenoma. All scores were calculated with the help of our library on predictions on a case basis. Conclusions: Our comprehensive and fastai-compatible library is helpful to standardize the workflow and minimize the burden of training a CNN. Indeed, our trained CNNs extracted neuropathologically relevant information from the WSI. This approach will supplement the clinicopathological diagnosis of brain tumors, which is currently based on cost-intensive microscopic examination and variable panels of immunohistochemical stainings.
CRIS-Team WoS Importer:2022-02-18

Biochemical markers of neurodegeneration in hereditary diffuse leucoencephalopathy with spheroids - Spitzer, Philipp; Kohl, Zacharias; Gölitz, Philipp; Coras, Roland; Blümcke, Ingmar; Brueck, Wolfgang; Dörfler, Arnd; Maihöfner, Christian (BMJ Case Reports, 2014)
Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare autosomal dominantly inherited disease with unknown pathophysiology. Diagnosis of neurodegenerative diseases is increasingly based on biomarkers. Although lumbar puncture is routinely performed during the diagnostic workup of HDLS, reports on alterations of neurodegeneration-specific biochemical markers have not been documented so far. We report a 35-year-old woman with clinical, radiological and neuropathological signs of HDLS. She suffered from a rapidly progressive frontal lobe syndrome. Brain MRI revealed diffuse leucoencephalopathy with predominant involvement of the periventricular white matter and corpus callosum. Although she was severely impaired and leucoencephalopathy was prominent, only cerebrospinal fluid total-? was moderately elevated. Other markers of neuronal (NSE) and astrocytic (S100B) damage were within normal range. Therefore, biochemical markers of central nervous system damage are not helpful in the diagnosis of HDL
EVALuna2:7264

Brain expression profiles of two SCN1A antisense RNAs in children and adolescents with epilepsy. - Schneider, Marius Frederik; Vogt, Miriam; Scheuermann, Johanna; Müller, Veronika; Fischer-Hentrich, Antje H.L.; Kremer, Thomas; Lugert, Sebastian; Metzger, Friedrich; Kudernatsch, Manfred; Kluger, Gerhard; Hartlieb, Till; Noachtar, Soheyl; et al. (Translational Neuroscience, 2024)
OBJECTIVE: Heterozygous mutations within the voltage-gated sodium channel α subunit (SCN1A) are responsible for the majority of cases of Dravet syndrome (DS), a severe developmental and epileptic encephalopathy. Development of novel therapeutic approaches is mandatory in order to directly target the molecular consequences of the genetic defect. The aim of the present study was to investigate whether cis-acting long non-coding RNAs (lncRNAs) of SCN1A are expressed in brain specimens of children and adolescent with epilepsy as these molecules comprise possible targets for precision-based therapy approaches. METHODS: We investigated SCN1A mRNA expression and expression of two SCN1A related antisense RNAs in brain tissues in different age groups of pediatric non-Dravet patients who underwent surgery for drug resistant epilepsy. The effect of different antisense oligonucleotides (ASOs) directed against SCN1A specific antisense RNAs on SCN1A expression was tested. RESULTS: The SCN1A related antisense RNAs SCN1A-dsAS (downstream antisense, RefSeq identifier: NR_110598) and SCN1A-usAS (upstream AS, SCN1A-AS, RefSeq identifier: NR_110260) were widely expressed in the brain of pediatric patients. Expression patterns revealed a negative correlation of SCN1A-dsAS and a positive correlation of lncRNA SCN1A-usAS with SCN1A mRNA expression. Transfection of SK-N-AS cells with an ASO targeted against SCN1A-dsAS was associated with a significant enhancement of SCN1A mRNA expression and reduction in SCN1A-dsAS transcripts. CONCLUSION: These findings support the role of SCN1A-dsAS in the suppression of SCN1A mRNA generation. Considering the haploinsufficiency in genetic SCN1A related DS, SCN1A-dsAS is an interesting target candidate for the development of ASOs (AntagoNATs) based precision medicine therapeutic approaches aiming to enhance SCN1A expression in DS.
EVALuna2:566168

Case Report: Consecutive Adrenal Cushing’s Syndrome and Cushing’s Disease in a Patient With Somatic CTNNB1, USP8, and NR3C1 Mutations - Detomas, Mario; Altieri, Barbara; Schlötelburg, Wiebke; Appenzeller, Silke; Schlaffer, Sven-Martin; Coras, Roland; Schirbel, Andreas; Wild, Vanessa; Kroiss, Matthias; Sbiera, Silviu; Fassnacht, Martin; Deutschbein, Timo (Frontiers in Endocrinology, 2021)
The occurrence of different subtypes of endogenous Cushing’s syndrome (CS) in single individuals is extremely rare. We here present the case of a female patient who was successfully cured from adrenal CS 4 years before being diagnosed with Cushing’s disease (CD). The patient was diagnosed at the age of 50 with ACTH-independent CS and a left-sided adrenal adenoma, in January 2015. After adrenalectomy and histopathological confirmation of a cortisol-producing adrenocortical adenoma, biochemical hypercortisolism and clinical symptoms significantly improved. However, starting from 2018, the patient again developed signs and symptoms of recurrent CS. Subsequent biochemical and radiological workup suggested the presence of ACTH-dependent CS along with a pituitary microadenoma. The patient underwent successful transsphenoidal adenomectomy, and both postoperative adrenal insufficiency and histopathological workup confirmed the diagnosis of CD. Exome sequencing excluded a causative germline mutation but showed somatic mutations of the β-catenin protein gene (CTNNB1) in the adrenal adenoma, and of both the ubiquitin specific peptidase 8 (USP8) and the glucocorticoid receptor (NR3C1) genes in the pituitary adenoma. In conclusion, our case illustrates that both ACTH-independent and ACTH-dependent CS may develop in a single individual even without evidence for a common genetic background.
CRIS-Team Scopus Importer:2021-09-17
Keywords: CTNNB1; Cushing’s disease; Cushing’s syndrome; glucocorticoid excess; hypercortisolism; NR3C1; USP8

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Clinical, surgical, and endocrine outcome following treatment of posterior pituitary tumors: a retrospective cohort study - Kremenevski, Natalia; Schnell, Oliver; Coras, Roland; Buchfelder, Michael; Hore, Nirjhar (Pituitary, 2025)
Purpose: This study evaluates the clinical presentation, endocrine dysfunction, surgical outcome, and long-term prognosis in patients with histologically confirmed posterior pituitary tumors (PPTs). Methods: A retrospective cohort study was conducted on 19 patients treated for PPTs at a single center between 2000 and 2023. Data on clinical, endocrine, and surgical outcomes were collected and analyzed. Results: The cohort included 3 pituicytomas (PCs), 8 granular cell tumors (GCTs), and 8 spindle cell oncocytomas (SCOs) patients, with a female predominance (58%) and a mean age of 57.2 ± 13.2 years. Symptoms leading to diagnosis were headache (31.6%), visual impairment (21%), and sexual dysfunction (10.5%). GCT patients had higher preoperative BMI (34.49 ± 5.72) compared to PC (22.12 ± 2.40) and SCO (24.74 ± 4.24) patients (p < 0.01). Postoperative BMI increased across all groups, with GCTs patients showing the steepest rise (p < 0.01). Endocrine dysfunction largely persisted or worsened after surgery, with limited recovery at follow-up. Surgical approaches included transsphenoidal (48%) and transcranial (52%), achieving gross total resection in 58% of cases. Tumor recurrence occurred in 16% of patients, all requiring adjuvant radiation therapy. Tumor-specific survival at 5 years was 100% with an overall survival rate of 80% where non-tumor-related comorbidities accounted for the observed mortality. Conclusion: PPTs are rare tumors with significant endocrine and metabolic consequences. While surgical management is associated with favorable tumor-specific survival, persistent endocrine dysfunction and postoperative progressive BMI underscore the need for long-term follow-up and targeted interventions. These findings contribute to the understanding of PPT biology and support the development of optimized management strategies.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Endocrine and surgical outcomes; Granular cell tumor; Pituicytoma; Pituitary function; Spindle cell oncocytoma

Commentary on the 1st International Summer School for Neuropathology and Epilepsy Surgery (INES 2013) held in Erlangen, Germany, September 16-20, 2013 - Blümcke, Ingmar; Coras, Roland (Epilepsia, 2014)
CRIS-Team Scopus Importer:2022-08-05

Complicated Clinical Course in Incipient Gigantism Due to Treatment-resistant Aryl Hydrocarbon Receptor–Interacting Protein–mutated Pediatric Somatotropinoma - van Santen, Selveta Sanne; Daly, Adrian F.; Buchfelder, Michael; Coras, Roland; Zhao, Yining; Beckers, Albert; van der Lely, Aart Jan; Hofland, Leo J.; Balvers, Rutger K.; van Koetsveld, P.; van den Heuvel-Eibrink, Marry Marrigje; Neggers, Sebastian Johannes Cornelis Martinus Maria (AACE Clinical Case Reports, 2022)
Background: Our objective was to describe the clinical course and treatment challenges in a very young patient with a pituitary adenoma due to a novel aryl hydrocarbon receptor–interacting protein (AIP) gene mutation, highlighting the limitations of somatostatin receptor immunohistochemistry to predict clinical responses to somatostatin analogs in acromegaly. Case Report: We report the case of a 7-year-old boy presenting with headache, visual field defects, and accelerated growth following failure to thrive. The laboratory results showed high insulin-like growth factor I (IGF-I) (standardised deviation scores (+3.49) and prolactin levels (0.5 nmol/L), and magnetic resonance imaging identified a pituitary macroadenoma. Tumoral/hormonal control could not be achieved despite 3 neurosurgical procedures, each time with apparent total resection or with lanreotide or pasireotide. IGF-I levels decreased with the GH receptor antagonist pegvisomant. The loss of somatostatin receptor 5 was observed between the second and third tumor resection. In vitro, no effect on tumoral GH release by pasireotide (with/without cabergoline) was observed. Genetic analysis revealed a novel germline AIP mutation: p.Tyr202∗ (pathogenic; class 4). Discussion: In vitro response of tumor tissue to somatostatin may better predict tumoral in vivo responses of somatostatin analogs than somatostatin receptor immunohistochemistry. Conclusion: We identified a novel pathologic AIP mutation that was associated with incipient acrogigantism in an extremely young patient who had a complicated course of disease. Growth acceleration can be masked due to failure to thrive. Tumoral growth hormone release in vivo may be predicted with in vitro exposure to somatostatin receptor analogs, as it cannot be assumed that all AIP-mutated somatotropinomas respond well to pasireotide.
CRIS-Team Scopus Importer:2022-02-11
Keywords: acromegaly; AIP mutation; gigantism; macroadenoma; pituitary adenoma; somatotropinoma

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05

Correction to: The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D (Acta Neuropathologica Communications, (2023), 11, 1, (129), 10.1186/s40478-023-01618-6) - Wang, Dan Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De Hong; Coras, Roland; Wang, Yu Jiao; Shi, Jie; Zhou, Wen Jing; Kobow, Katja; Piao, Yue Shan (Acta Neuropathologica Communications, 2024)
Following publication of the original article [1], the authors identified errors in the reference list and citations. Due to a technical error a wrong article version for the references and citations was used. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2024-04-05

DCX+ neuronal progenitors contribute to new oligodendrocytes during remyelination in the hippocampus - Klein, Barbara; Mrowetz, Heike; Kreutzer, Christina; Rotheneichner, Peter; Zaunmair, Pia; Lange, Simona; Coras, Roland; Couillard-Despres, Sebastien; Rivera, Francisco J.; Aigner, Ludwig (Scientific Reports, 2020)
A pool of different types of neural progenitor cells resides in the adult hippocampus. Apart from doublecortin-expressing (DCX+) neuronal progenitor cells (NPCs), the hippocampal parenchyma also contains oligodendrocyte precursor cells (OPCs), which can differentiate into myelinating oligodendrocytes. It is not clear yet to what extent the functions of these different progenitor cell types overlap and how plastic these cells are in response to pathological processes. The aim of this study was to investigate whether hippocampal DCX+ NPCs can generate new oligodendrocytes under conditions in which myelin repair is required. For this, the cell fate of DCX-expressing NPCs was analyzed during cuprizone-induced demyelination and subsequent remyelination in two regions of the hippocampal dentate gyrus of DCX-CreERT2/Flox-EGFP transgenic mice. In this DCX reporter model, the number of GFP+ NPCs co-expressing Olig2 and CC1, a combination of markers typically found in mature oligodendrocytes, was significantly increased in the hippocampal DG during remyelination. In contrast, the numbers of GFP+PDGFRα+ cells, as well as their proliferation, were unaffected by de- or remyelination. During remyelination, a higher portion of newly generated BrdU-labeled cells were GFP+ NPCs and there was an increase in new oligodendrocytes derived from these proliferating cells (GFP+Olig2+BrdU+). These results suggest that DCX-expressing NPCs were able to contribute to the generation of mature oligodendrocytes during remyelination in the adult hippocampus.
CRIS-Team Scopus Importer:2020-11-27

Deep histopathology genotype–phenotype analysis of focal cortical dysplasia type II differentiates between the GATOR1-altered autophagocytic subtype IIa and MTOR-altered migration deficient subtype IIb - Honke, Jonas; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Leu, Costin; Pieper, Tom; Hartlieb, Till; Bien, Christian G.; Woermann, Friedrich; Cloppenborg, Thomas; Kalbhenn, Thilo; Gaballa, Ahmed; et al. (Acta Neuropathologica Communications, 2023)
Focal cortical dysplasia type II (FCDII) is the most common cause of drug-resistant focal epilepsy in children. Herein, we performed a deep histopathology-based genotype–phenotype analysis to further elucidate the clinico-pathological and genetic presentation of FCDIIa compared to FCDIIb. Seventeen individuals with histopathologically confirmed diagnosis of FCD ILAE Type II and a pathogenic variant detected in brain derived DNA whole-exome sequencing or mTOR gene panel sequencing were included in this study. Clinical data were directly available from each contributing centre. Histopathological analyses were performed from formalin-fixed, paraffin-embedded tissue samples using haematoxylin–eosin and immunohistochemistry for NF-SMI32, NeuN, pS6, p62, and vimentin. Ten individuals carried loss-of-function variants in the GATOR1 complex encoding genes DEPDC5 (n = 7) and NPRL3 (n = 3), or gain-of-function variants in MTOR (n = 7). Whereas individuals with GATOR1 variants only presented with FCDIIa, i.e., lack of balloon cells, individuals with MTOR variants presented with both histopathology subtypes, FCDIIa and FCDIIb. Interestingly, 50% of GATOR1-positive cases showed a unique and predominantly vacuolizing phenotype with p62 immunofluorescent aggregates in autophagosomes. All cases with GATOR1 alterations had neurosurgery in the frontal lobe and the majority was confined to the cortical ribbon not affecting the white matter. This pattern was reflected by subtle or negative MRI findings in seven individuals with GATOR1 variants. Nonetheless, all individuals were seizure-free after surgery except four individuals carrying a DEPDC5 variant. We describe a yet underrecognized genotype–phenotype correlation of GATOR1 variants with FCDIIa in the frontal lobe. These lesions were histopathologically characterized by abnormally vacuolizing cells suggestive of an autophagy-altered phenotype. In contrast, individuals with FCDIIb and brain somatic MTOR variants showed larger lesions on MRI including the white matter, suggesting compromised neural cell migration.
CRIS-Team Scopus Importer:2023-11-17

Defining clinico-neuropathological subtypes of mesial temporal lobe epilepsy with hippocampal sclerosis - Blümcke, Ingmar; Coras, Roland; Miyata, Hajime; Özkara, Cigdem (Brain Pathology, 2012)
Hippocampal sclerosis (HS) is the most frequent cause of drug-resistant focal epilepsies (ie, mesial temporal lobe epilepsy with hippocampal sclerosis; mTLE-HS), and presents a broad spectrum of electroclinical, structural and molecular pathology patterns. Many patients become drug resistant during the course of the disease, and surgical treatment was proven helpful to achieve seizure control. Hence, up to 40% of patients suffer from early or late surgical failures. Different patterns of hippocampal cell loss, involvement of other mesial temporal structures, as well as temporal neocortex including focal cortical dysplasia, may contribute to the extent of the epileptogenic network and will be discussed. An international consensus is mandatory to clarify terminology use and to reliably distinguish mTLE-HS subtypes. High-resolution imaging with confirmed histopathologic diagnosis, as well as advanced neurophysiologic and molecular genetic measures, will be a powerful tool in the future to address these issues and help to predict each patient's probability to control their epilepsy in mTLE-HS conditions. © 2012 The Authors; © 2012 International Society of Neuropathology.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Development; Hippocampus; Mesial temporal sclerosis; Neuropathology; Seizure

Defining the role of surgery for patients with multiple brain metastases - Ersoy, Tunc Faik; Brainman, Daniel; Coras, Roland; Berger, Björn; Weissinger, Florian; Grote, Alexander; Simon, Matthias (Journal of Neuro-Oncology, 2024)
Purpose: To better define the role of surgery, we investigated survival and functional outcomes in patients with multiple brain metastases. Methods: Pertinent clinical and radiological data of 131 consecutive patients (156 surgeries) were analyzed retrospectively. Results: Surgical indications included mass effect (84.6%) and need for tissue acquisition (44.9%, for molecularly informed treatment: 10 patients). Major (i.e. CTCAE grade 3–5) neurological, surgical and medical complication were observed in 6 (3.8%), 12 (7.7%), and 12 (7.7%) surgical cases. Median preoperative and discharge KPS were 80% (IQF: 60–90%). Median overall survival (mOS) was 7.4 months. However, estimated 1 and 2 year overall survival rates were 35.6% and 25.1%, respectively. Survival was dismal (i.e. mOS ≤ 2.5 months) in patients who had no postoperative radio- and systemic therapy, or who incurred major complications. Multivariate analysis with all parameters significantly correlated with survival as univariate parameters revealed female sex, oligometastases, no major new/worsened neurological deficits, and postoperative radio- and systemic therapy as independent positive prognostic parameters. Univariate positive prognostic parameters also included histology (best survival in breast cancer patients) and less than median (0.28 cm3) residual tumor load. Conclusions: Surgery is a reasonable therapeutic option in many patients with multiple brain metastases. Operations should primarily aim at reducing mass effect thereby preserving the patients’ functional health status which will allow for further local (radiation) and systemic therapy. Surgery for the acquisition of metastatic tissue (more recently for molecularly informed treatment) is another important surgical indication. Cytoreductive surgery may also carry a survival benefit by itself.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Complications; Cytoreduction; Functional outcome; Multiple brain metastases; Prognosis; Surgery

D-galactose Supplementation for the Treatment of Mild Malformation of Cortical Development with Oligodendroglial Hyperplasia in Epilepsy (MOGHE): A Pilot Trial of Precision Medicine After Epilepsy Surgery - Aledo-Serrano, Ángel; Valls-Carbó, Adrián; Fenger, Christina D.; Groeppel, Gudrun; Hartlieb, Till; Pascual, Irene; Herraez, Erika; Cabal, Borja; García-Morales, Irene; Toledano, Rafael; Budke, Marcelo; Beltran-Corbellini, Álvaro; et al. (Neurotherapeutics, 2023)
MOGHE is defined as mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy. Approximately half of the patients with histopathologically confirmed MOGHE carry a brain somatic variant in the SLC35A2 gene encoding a UDP-galactose transporter. Previous research showed that D-galactose supplementation results in clinical improvement in patients with a congenital disorder of glycosylation due to germline variants in SLC35A2. We aimed to evaluate the effects of D-galactose supplementation in patients with histopathologically confirmed MOGHE, with uncontrolled seizures or cognitive impairment and epileptiform activity at the EEG after epilepsy surgery (NCT04833322). Patients were orally supplemented with D-galactose for 6 months in doses up to 1.5 g/kg/day and monitored for seizure frequency including 24-h video-EEG recording, cognition and behavioral scores, i.e., WISC, BRIEF-2, SNAP-IV, and SCQ, and quality of life measures, before and 6 months after treatment. Global response was defined by > 50% improvement of seizure frequency and/or cognition and behavior (clinical global impression of “much improved” or better). Twelve patients (aged 5–28 years) were included from three different centers. Neurosurgical tissue samples were available in all patients and revealed a brain somatic variant in SLC35A2 in six patients (non-present in the blood). After 6 months of supplementation, D-galactose was well tolerated with just two patients presenting abdominal discomfort, solved after dose spacing or reduction. There was a 50% reduction or higher of seizure frequency in 3/6 patients, with an improvement at EEG in 2/5 patients. One patient became seizure-free. An improvement of cognitive/behavioral features encompassing impulsivity (mean SNAP-IV − 3.19 [− 0.84; − 5.6]), social communication (mean SCQ − 2.08 [− 0.63; − 4.90]), and executive function (BRIEF-2 inhibit − 5.2 [− 1.23; − 9.2]) was observed. Global responder rate was 9/12 (6/6 in SLC35A2-positive). Our results suggest that supplementation with D-galactose in patients with MOGHE is safe and well tolerated and, although the efficacy data warrant larger studies, it might build a rationale for precision medicine after epilepsy surgery.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Developmental and epileptic encephalopathy; Genetic epilepsy; Neurogenetics; SLC35A2; Somatic mutation

D-galactose supplementation for the treatment of patients with mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE): An interim analysis of a proof-of-concept trial - Aledo-Serrano, A.; Toledano, R.; Garcia-Morales, I.; Budke, M.; Beltran-Corbellini, A.; Blumcke, I.; Coras, Roland; Gil-Nagel, A. (EPILEPSIA, 2022)
CRIS-Team WoS Importer:2022-09-30

Disseminated Multifocal Intracerebral Bleeding Events in Three Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation As Rescue Therapy. - Bihlmaier, Karl; Coras, Roland; Willam, Carsten; Grampp, Steffen; Jabari, Samir; Eichhorn, Philip; Haller, Florian; Kuramatsu, Joji; Schwab, Stefan; Castellanos, Ixchel; Birkholz, Torsten; Schüttler, Jürgen; et al. (Critical Care Explorations, 2020)
Objectives: To describe three coronavirus disease 2019 patients suffering from acute respiratory distress syndrome under venovenous extracorporeal membrane oxygenation therapy and tight anticoagulation monitoring presenting a novel pattern of multifocal brain hemorrhage in various degrees in all cerebral and cerebellar lobes. Design: Clinical observation of three patients. Post mortem examinations. Setting: Two ICUs at the University Hospital Erlangen. Patients: Three patients (medium age 56.6 yr, two male with hypertension and diabetes, one female with no medical history) developed severe acute respiratory distress syndrome on the basis of a severe acute respiratory syndrome coronavirus 2 infection. All required mechanical ventilation and venovenous extracorporeal membrane oxygenation support. Interventions: Clinical observation, CT, data extraction from electronic medical records, and post mortem examinations. Main Results: We report on an unusual multifocal bleeding pattern in the white matter in three cases with severe acute respiratory distress syndrome due to coronavirus disease 2019 undergoing venovenous extracorporeal membrane oxygenation therapy. Bleeding pattern with consecutive herniation was found in CT scans as well as in neuropathologic post mortem examinations. Frequency for this unusual brain hemorrhage in coronavirus disease 2019 patients with extracorporeal membrane oxygenation therapy at our hospital is currently 50%, whereas bleeding events in extracorporeal membrane oxygenation patients generally occur at 10-15%. Conclusions: Multifocality and high frequency of the unusual white matter hemorrhage pattern suggest a coherence to coronavirus disease 2019. Neuropathological analyses showed circumscribed thrombotic cerebrovascular occlusions, which eventually led to microvascular and later on macrovascular disseminated bleeding events. However, signs of cerebrovascular inflammation could not be detected. Polymerase chain reaction analyses of brain tissue or cerebrospinal fluid remained negative. Increased susceptibility for fatal bleeding events should be taken into consideration in terms of systemic anticoagulation strategies in coronavirus disease 2019.
EVALuna2:313697
Keywords: acute respiratory distress syndrome; cerebral microhemorrhage; coronavirus disease 2019; extracorporeal membrane oxygenation; intracerebral bleeding

Distinct DNA Methylation Patterns of Subependymal Giant Cell Astrocytomas in Tuberous Sclerosis Complex - Bongaarts, Anika; Mijnsbergen, Caroline; Anink, Jasper J.; Jansen, Floor E.; Spliet, Wim G.M.; den Dunnen, Wilfred F.A.; Coras, Roland; Blümcke, Ingmar; Paulus, Werner; Gruber, Victoria E.; Scholl, Theresa; Hainfellner, Johannes A.; et al. (Cellular and Molecular Neurobiology, 2021)
Tuberous sclerosis complex (TSC) is a monogenic disorder caused by mutations in either the TSC1 or TSC2 gene, two key regulators of the mechanistic target of the rapamycin complex pathway. Phenotypically, this leads to growth and formation of hamartomas in several organs, including the brain. Subependymal giant cell astrocytomas (SEGAs) are low-grade brain tumors commonly associated with TSC. Recently, gene expression studies provided evidence that the immune system, the MAPK pathway and extracellular matrix organization play an important role in SEGA development. However, the precise mechanisms behind the gene expression changes in SEGA are still largely unknown, providing a potential role for DNA methylation. We investigated the methylation profile of SEGAs using the Illumina Infinium HumanMethylation450 BeadChip (SEGAs n = 42, periventricular control n = 8). The SEGA methylation profile was enriched for the adaptive immune system, T cell activation, leukocyte mediated immunity, extracellular structure organization and the ERK1 & ERK2 cascade. More interestingly, we identified two subgroups in the SEGA methylation data and show that the differentially expressed genes between the two subgroups are related to the MAPK cascade and adaptive immune response. Overall, this study shows that the immune system, the MAPK pathway and extracellular matrix organization are also affected on DNA methylation level, suggesting that therapeutic intervention on DNA level could be useful for these specific pathways in SEGA. Moreover, we identified two subgroups in SEGA that seem to be driven by changes in the adaptive immune response and MAPK pathway and could potentially hold predictive information on target treatment response.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Low-grade glioma; Methylation; RNA-sequencing; SEGA; TSC

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

Dynamic expression of NR2F1 and SOX2 in developing and adult human cortex: comparison with cortical malformations - Foglio, Benedetta; Rossini, Laura; Garbelli, Rita; Regondi, Maria Cristina; Mercurio, Sara; Bertacchi, Michele; Avagliano, Laura; Bulfamante, Gaetano; Coras, Roland; Maiorana, Antonino; Nicolis, Silvia; Studer, Michèle; et al. (Brain Structure & Function, 2021)
The neocortex, the most recently evolved brain region in mammals, is characterized by its unique areal and laminar organization. Distinct cortical layers and areas can be identified by the presence of graded expression of transcription factors and molecular determinants defining neuronal identity. However, little is known about the expression of key master genes orchestrating human cortical development. In this study, we explored the expression dynamics of NR2F1 and SOX2, key cortical genes whose mutations in human patients cause severe neurodevelopmental syndromes. We focused on physiological conditions, spanning from mid-late gestational ages to adulthood in unaffected specimens, but also investigated gene expression in a pathological context, a developmental cortical malformation termed focal cortical dysplasia (FCD). We found that NR2F1 follows an antero-dorsallow to postero-ventralhigh gradient as in the murine cortex, suggesting high evolutionary conservation. While SOX2 is mainly expressed in neural progenitors next to the ventricular surface, NR2F1 is found in both mitotic progenitors and post-mitotic neurons at GW18. Interestingly, both proteins are highly co-expressed in basal radial glia progenitors of the outer sub-ventricular zone (OSVZ), a proliferative region known to contribute to cortical expansion and complexity in humans. Later on, SOX2 becomes largely restricted to astrocytes and oligodendrocytes although it is also detected in scattered mature interneurons. Differently, NR2F1 maintains its distinct neuronal expression during the whole process of cortical development. Notably, we report here high levels of NR2F1 in dysmorphic neurons and NR2F1 and SOX2 in balloon cells of surgical samples from patients with FCD, suggesting their potential use in the histopathological characterization of this dysplasia.
CRIS-Team Scopus Importer:2021-03-19
Keywords: BBSOAS; Cortical dysplasia; Human cortical development; NR2F1/COUP-TF1; SOX2; Transcription factors

Dysmorphic neurons as cellular source for phase-amplitude coupling in Focal Cortical Dysplasia Type II - Rampp, Stefan; Rössler, Karl; Hamer, Hajo; Illek, Margit; Buchfelder, Michael; Dörfler, Arnd; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Kölble, Konrad; Peixoto-Santos, Jose Eduardo; Blümcke, Ingmar; et al. (Clinical Neurophysiology, 2021)
Objective: Reliable localization of the epileptogenic zone is necessary for successful epilepsy surgery. Neurophysiological biomarkers include ictal onsets and interictal spikes. Furthermore, the epileptic network shows oscillations with potential localization value and pathomechanistic implications. The cellular origin of such markers in invasive EEG in vivo remains to be clarified. Methods: In the presented pilot study, surgical brain samples and invasive EEG recordings of seven patients with surgically treated Focal Cortical Dysplasia (FCD) type II were coregistered using a novel protocol. Dysmorphic neurons and balloon cells were immunohistochemically quantified. Evaluated markers included seizure onset, spikes, and oscillatory activity in delta, theta, gamma and ripple frequency bands, as well as sample entropy and phase-amplitude coupling between delta, theta, alpha and beta phase and gamma amplitude. Results: Correlations between histopathology and neurophysiology provided evidence for a contribution of dysmorphic neurons to interictal spikes, fast gamma activity and ripples. Furthermore, seizure onset and phase-amplitude coupling in areas with dysmorphic neurons suggests preserved connectivity is related to seizure initiation. Balloon cells showed no association. Conclusions: Phase-amplitude coupling, spikes, fast gamma and ripples are related to the density of dysmorphic neurons and localize the seizure onset zone. Significance: The results of our pilot study provide a new powerful tool to address the cellular source of abnormal neurophysiology signals to leverage current and novel biomarkers for the localization of epileptic activity in the human brain.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Electrophysiological markers; Epilepsy; Focal cortical dysplasia; Invasive EEG

Early postoperative seizures (EPS) in patients undergoing brain tumour surgery - Ersoy, Tunc Faik; Ridwan, Sami; Grote, Alexander; Coras, Roland; Simon, Matthias (Scientific Reports, 2020)
Early postoperative seizures (EPS) are a common complication of brain tumour surgery. This paper investigates risk factors, management and clinical relevance of EPS. We retrospectively analysed the occurrence of EPS, clinical and laboratory parameters, imaging and histopathological findings in a cohort of 679 consecutive patients who underwent craniotomies for intracranial tumours between 2015 and 2017. EPS were observed in 34/679 cases (5.1%), with 14 suffering at least one generalized seizure. Patients with EPS had a worse postoperative Karnofsky performance index (KPI; with EPS, KPI < 70 vs. 70–100: 11/108, 10.2% vs. 23/571, 4.0%; p = 0.007). Preoperative seizure history was a predictor for EPS (none vs. 1 vs. ≥ 2 seizures: p = 0.037). Meningioma patients had the highest EPS incidence (10.1%, p < 0.001). Cranial imaging identified a plausible cause in most cases (78.8%). In 20.6%, EPS were associated with a persisting new neurological deficit that could not otherwise be explained. 34.6% of the EPS patients had recurrent seizures within one year. EPS require an emergency work-up. Multiple EPS and recurrent seizures are frequent, which indicates that EPS may also reflect a more chronic condition i.e. epilepsy. EPS are often associated with persisting neurological worsening.
CRIS-Team Scopus Importer:2020-08-28

Epileptogene Hirntumoren: Erkenntnisse aus neuropathologischen Untersuchungen - Blümcke, Ingmar; Coras, Roland (Zeitschrift für Epileptologie, 2012)
A distinct group of brain neoplasias can be identified in 26.5% of all patients with chronic focal epilepsies undergoing epilepsy surgery. These tumors often present with an unusual histomorphological spectrum and have been designated as long-term epilepsy-associated tumors (LEAT), i.e., gangliogliomas and dysembryoplastic neuroepithelial tumors. Our series of patients were operated at a mean age of 25.4 years and had suffered from drug-resistant epilepsy for 12.6 years. Surgical tumor specimens open the possibility to address the origin and epileptogenicity of LEAT. Intriguingly, most studies failed to identify common tumor-associated genetic aberrations. In contrast, neurodevelopmentally regulated genes related to mammalian target of rapamycin (mTOR) or reelin signaling pathways are likely to play key roles and may also be involved in associated focal cortical dysplasias (FCD). Thus, research analysis of LEAT opens new avenues for understanding brain development under physiological as well as pathophysiological conditions. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Epilepsy; Immunohistochemistry; Molecular pathology; Neuroepithelial tumors

Evidence for postnatal neurogenesis in the human amygdala - Röder, Sebastian; Burkardt, Petra; Rost, Fabian; Rode, Julian; Brusch, Lutz; Coras, Roland; Englund, Elisabet; Håkansson, Karl; Possnert, Göran; Salehpour, Mehran; Primetzhofer, Daniel; Csiba, László; et al. (Communications Biology, 2022)
The human amygdala is involved in processing of memory, decision-making, and emotional responses. Previous studies suggested that the amygdala may represent a neurogenic niche in mammals. By combining two distinct methodological approaches, lipofuscin quantification and 14C-based retrospective birth dating of neurons, along with mathematical modelling, we here explored whether postnatal neurogenesis exists in the human amygdala. We investigated post-mortem samples of twelve neurologically healthy subjects. The average rate of lipofuscin-negative neurons was 3.4%, representing a substantial proportion of cells substantially younger than the individual. Mass spectrometry analysis of genomic 14C-concentrations in amygdala neurons compared with atmospheric 14C-levels provided evidence for postnatal neuronal exchange. Mathematical modelling identified a best-fitting scenario comprising of a quiescent and a renewing neuronal population with an overall renewal rate of >2.7% per year. In conclusion, we provide evidence for postnatal neurogenesis in the human amygdala with cell turnover rates comparable to the hippocampus.
CRIS-Team Scopus Importer:2022-04-29

First report from the German COVID-19 autopsy registry - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; Knüchel, Ruth; et al. (The Lancet Regional Health - Europe, 2022)
Background: Autopsies are an important tool in medicine, dissecting disease pathophysiology and causes of death. In COVID-19, autopsies revealed e.g., the effects on pulmonary (micro)vasculature or the nervous system, systemic viral spread, or the interplay with the immune system. To facilitate multicentre autopsy-based studies and provide a central hub supporting autopsy centres, researchers, and data analyses and reporting, in April 2020 the German COVID-19 Autopsy Registry (DeRegCOVID) was launched. Methods: The electronic registry uses a web-based electronic case report form. Participation is voluntary and biomaterial remains at the respective site (decentralized biobanking). As of October 2021, the registry included N=1129 autopsy cases, with 69271 single data points including information on 18674 available biospecimens gathered from 29 German sites. Findings: In the N=1095 eligible records, the male-to-female ratio was 1·8:1, with peaks at 65-69 and 80-84 years in males and >85 years in females. The analysis of the chain of events directly leading to death revealed COVID-19 as the underlying cause of death in 86% of the autopsy cases, whereas in 14% COVID-19 was a concomitant disease. The most common immediate cause of death was diffuse alveolar damage, followed by multi-organ failure. The registry supports several scientific projects, public outreach and provides reports to the federal health authorities, leading to legislative adaptation of the German Infection Protection Act, facilitating the performance of autopsies during pandemics. Interpretation: A national autopsy registry can provide multicentre quantitative information on COVID-19 deaths on a national level, supporting medical research, political decision-making and public discussion. Funding: German Federal Ministries of Education and Research and Health. Hintergrund: Obduktionen sind ein wichtiges Instrument in der Medizin, um die Pathophysiologie von Krankheiten und Todesursachen zu untersuchen. Im Rahmen von COVID-19 wurden durch Obduktionen z.B. die Auswirkungen auf die pulmonale Mikrovaskulatur, das Nervensystem, die systemische Virusausbreitung, und das Zusammenspiel mit dem Immunsystem untersucht. Um multizentrische, auf Obduktionen basierende Studien zu erleichtern und eine zentrale Anlaufstelle zu schaffen, die Obduktionszentren, Forscher sowie Datenanalysen und -berichte unterstützt, wurde im April 2020 das deutsche COVID-19-Autopsieregister (DeRegCOVID) ins Leben gerufen. Methoden: Das elektronische Register verwendet ein webbasiertes elektronisches Fallberichtsformular. Die Teilnahme ist freiwillig und das Biomaterial verbleibt am jeweiligen Standort (dezentrales Biobanking). Im Oktober 2021 umfasste das Register N=1129 Obduktionsfälle mit 69271 einzelnen Datenpunkten, die Informationen über 18674 verfügbare Bioproben enthielten, die von 29 deutschen Standorten gesammelt wurden. Ergebnisse: In den N=1095 ausgewerteten Datensätzen betrug das Verhältnis von Männern zu Frauen 1,8:1 mit Spitzenwerten bei 65-69 und 80-84 Jahren bei Männern und >85 Jahren bei Frauen. Die Analyse der Sequenz der unmittelbar zum Tod führenden Ereignisse ergab, dass in 86 % der Obduktionsfälle COVID-19 die zugrunde liegende Todesursache war, während in 14 % der Fälle COVID-19 eine Begleiterkrankung war. Die häufigste unmittelbare Todesursache war der diffuse Alveolarschaden, gefolgt von Multiorganversagen. Das Register unterstützt mehrere wissenschaftliche Projekte, die Öffentlichkeitsarbeit und liefert Berichte an die Bundesgesundheitsbehörden, was zu einer Anpassung des deutschen Infektionsschutzgesetzes führte und die Durchführung von Obduktionen in Pandemien erleichtert. Interpretation: Ein nationales Obduktionsregister kann multizentrische quantitative Informationen über COVID-19-Todesfälle auf nationaler Ebene liefern und damit die medizinische Forschung, die politische Entscheidungsfindung und die öffentliche Diskussion unterstützen. Finanzierung: Bundesministerien für Bildung und Forschung und für Gesundheit.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Autopsy; Cause of Death; COVID-19; Registry; SARS-CoV-2

Focal cortical dysplasia type 1 - Coras, Roland; Holthausen, Hans; Sarnat, Harvey B. (Brain Pathology, 2021)
The ILAE classification of Focal Cortical Dysplasia (FCD) from 2011 has quickly gained acceptance in clinical practice and research and is now widely used around the world. This histopathology-based classification scheme proposed three subtypes, that is, FCD Type 1 (with architectural abnormalities of the neocortex), FCD Type 2 (with cytoarchitectural abnormalities of the neocortex) and FCD Type 3 (architectural abnormalities of the neocortex associated with another principle lesion acquired during early life). Valuable knowledge was gathered during the last decade validating the clinical, pathological and genetic classification of FCD Type 2. This is in contrast to FCD subtype 1 and 3 with only few robust or new insights. Herein, we provide an overview about current knowledge about FCD Type 1 and its three subtypes. Available data strengthened, however, FCD Type 1A in particular, whereas a comprehensive clinico-pathological specification for FCD Type 1B and 1C subtypes remain to be shown. The lack of a valid animal model for FCD Type 1 further supports our call and the ongoing need for systematic research studies based on a careful clinico-pathological and genetic stratification of patients and human brain tissues.
CRIS-Team Scopus Importer:2021-07-16
Keywords: focal cortical dysplasia type 1

Frontal lobe epilepsy and mild malformation with oligodendroglial hyperplasia: Further observations on electroclinical and imaging phenotypes, and surgical perspectives - Garganis, Kyriakos; Gkiatis, Kostakis; Maletic, Jelena; Harushukuri, Jean; Kondylidis, Nikolaos; Dinopoulos, Argiris; Vorgia, Pelagia; Coras, Roland; Blümcke, Ingmar; Zountsas, Basilios (Epileptic Disorders, 2023)
Objective: Mild malformation with oligodendroglial hyperplasia (MOGHE) is a recently described clinicopathologic entity, associated with drug-resistant epilepsy and extensive epileptogenic networks. Knowledge is accumulating about particular electroclinical phenotypes, correlations with imaging, and potential prognostic significance for surgical outcomes. The study adds relevant information by documenting the presence of a hyperkinetic frontal lobe seizure phenotype in adolescents and an epileptic encephalopathy phenotype in young children. Methods: Five cases were subjected to a structured presurgical evaluation protocol, including EEG-FMRI, chronic and acute invasive EEG, subjected to frontal lobe surgery with postoperative follow-up between 15 months and 7 years. Results: In the two adult cases, surface EEG demonstrated lateralized widespread frontal lobe epileptogenicity and hyperkinetic semiological features. MRI demonstrated cortical white matter blurring and deeper white matter abnormalities. EEG-FMRI suggested concordant frontal lobe involvement. iEEG demonstrated a widespread frontal lobe epilepsy network. The three young children demonstrated a diffuse epileptic encephalopathy phenotype, with nonlocalizing, nonlateralizing surface EEG, and “spasms” as the main seizure type. MRI demonstrated extensive frontal lobe subcortical gray and white matter abnormalities, consistent with MOGHE literature for this age, while EEG-FMRI, in 2/3, demonstrated concordant frontal lobe involvement. They did not undergo chronic iEEG, and the resection was assisted by acute intraoperative ECoG. All cases were subjected to extensive frontal lobectomies with Engel class IA (2/5), IB (1/5), and IIB (2/5) outcomes. Significance: The study confirms the presence of frontal lobe epilepsy and epileptic encephalopathy phenotypes, in accordance with epilepsy phenotypes already described in MOGHE literature. Presurgical evaluation studies, including EEG-FMRI, can provide strong lateralizing and localizing evidence of the epileptogenic networks involved. All responded favorably to extensive frontal lobe resections, despite widespread epileptic activity recorded by surface and intracranial EEG pre- and postoperatively; an epileptic encephalopathy phenotype, in the first years of life, should not discourage such a resection.
CRIS-Team Scopus Importer:2023-05-19
Keywords: cortical dysplasia; EEG-fMRI; epilepsy surgery; epileptic encephalopathy; hyperkinetic seizures

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

Genetic and epigenetic characterization of posterior pituitary tumors - Schmid, Simone; Solomon, David A.; Perez, Eilis; Thieme, Anne; Kleinschmidt-Demasters, Bette K.; Giannini, Caterina; Reinhardt, Annekathrin; Asa, Sylvia L.; Mete, Ozgur; Stichel, Damian; Siewert, Christin; Dittmayer, Carsten; et al. (Acta Neuropathologica, 2021)
Pituicytoma (PITUI), granular cell tumor (GCT), and spindle cell oncocytoma (SCO) are rare tumors of the posterior pituitary. Histologically, they may be challenging to distinguish and have been proposed to represent a histological spectrum of a single entity. We performed targeted next-generation sequencing, DNA methylation profiling, and copy number analysis on 47 tumors (14 PITUI; 12 GCT; 21 SCO) to investigate molecular features and explore possibilities of clinically meaningful tumor subclassification. We detected two main epigenomic subgroups by unsupervised clustering of DNA methylation data, though the overall methylation differences were subtle. The largest group (n = 23) contained most PITUIs and a subset of SCOs and was enriched for pathogenic mutations within genes in the MAPK/PI3K pathways (12/17 [71%] of sequenced tumors: FGFR1 (3), HRAS (3), BRAF (2), NF1 (2), CBL (1), MAP2K2 (1), PTEN (1)) and two with accompanying TERT promoter mutation. The second group (n = 16) contained most GCTs and a subset of SCOs, all of which mostly lacked identifiable genetic drivers. Outcome analysis demonstrated that the presence of chromosomal imbalances was significantly associated with reduced progression-free survival especially within the combined PITUI and SCO group (p = 0.031). In summary, we observed only subtle DNA methylation differences between posterior pituitary tumors, indicating that these tumors may be best classified as subtypes of a single entity. Nevertheless, our data indicate differences in mutation patterns and clinical outcome. For a clinically meaningful subclassification, we propose a combined histo-molecular approach into three subtypes: one subtype is defined by granular cell histology, scarcity of identifiable oncogenic mutations, and favorable outcome. The other two subtypes have either SCO or PITUI histology but are segregated by chromosomal copy number profile into a favorable group (no copy number changes) and a less favorable group (copy number imbalances present). Both of the latter groups have recurrent MAPK/PI3K genetic alterations that represent potential therapeutic targets.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Brain tumor; Granular cell tumor; Molecular neuropathology; Pituicytoma; Posterior pituitary gland neoplasms; Spindle cell oncocytoma

Glucocorticoid modulation of synaptic plasticity in the human temporal cortex of epilepsy patients: Does chronic stress contribute to memory impairment? - Brandner, Sebastian; Schröter, Sarah; Çalışkan, Gürsel; Salar, Seda; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Schwarz, Michael; Buchfelder, Michael; Maslarova, Anna (Epilepsia, 2021)
Objective: Memory impairment is common in patients with temporal lobe epilepsy and seriously affects life quality. Chronic stress is a recognized cofactor in epilepsy and can also impair memory function. Furthermore, increased cortisol levels have been reported in epilepsy patients. Animal models have suggested that aggravating effects of stress on memory and synaptic plasticity were mediated via glucocorticoids. The aim of this study was, therefore, to investigate the effect of glucocorticoid receptor (GR) modulation on synaptic plasticity in the human cortex of epilepsy patients. Methods: We performed field potential recordings in acute slices from the temporal neocortex of patients who underwent surgery for drug-resistant temporal lobe epilepsy. Synaptic plasticity was investigated by a theta-burst stimulation (TBS) protocol for induction of long-term potentiation (LTP) in the presence of GR modulators. Results: LTP was impaired in temporal cortex from epilepsy patients. Pretreatment of the slices with the GR antagonist mifepristone (RU486) improved LTP induction, suggesting that LTP impairment was due to baseline GR activation in the human cortex. The highly potent GR agonist dexamethasone additionally weakened synaptic strength in an activity-dependent manner when applied after TBS. Significance: Our results show a direct negative glucocorticoid effect on synaptic potentiation in the human cortex and imply chronic activation of GRs. Chronic stress may therefore contribute to memory impairment in patients with temporal lobe epilepsy. Furthermore, the activity-dependent acute inhibitory effect of dexamethasone suggests a mechanism of synaptic downscaling by which postictally increased cortisol levels may prevent pathologic plasticity upon seizures.
CRIS-Team Scopus Importer:2021-10-29
Keywords: dexamethasone; epilepsy; human cortex; long-term potentiation; stress

Good interobserver and intraobserver agreement in the evaluation of the new ILAE classification of focal cortical dysplasias - Coras, Roland; De Boer, Onno J.; Armstrong, Dawna; Becker, Albert; Jacques, Thomas S.; Miyata, Hajime; Thom, Maria; Vinters, Harry V.; Spreafico, Roberto; Oz, Buge; Marucci, Gianluca; Pimentel, Jose; et al. (Epilepsia, 2012)
Summary Purpose: An International League Against Epilepsy (ILAE) consensus classification system for focal cortical dysplasias (FCDs) has been published in 2011 specifying clinicopathologic FCD variants. The aim of the present work was to microscopically assess interobserver agreement and intraobserver reproducibility for FCD categories among an international group of neuropathologists with different levels of experience and access to epilepsy surgery tissue. Methods: Surgical FCD specimens covering a broad histopathology spectrum were retrieved from 22 patients with epilepsy. Three surgical nonepilepsy specimens served as controls. A total of 188 slides with routine or immunohistochemical stainings were digitalized with a slide scanner to allow Internet-based microscopy review. Nine experienced neuropathologists were invited to review these cases twice at a time gap of 3 months and different orders of case presentation. The 2011 ILAE FCD consensus classification served as instruction. Kappa analysis was calculated to estimate interobserver and intraobserver agreement levels. In a third evaluation round, 21 additional neuropathologists with different experience and access to epilepsy surgery reviewed the same case series. Key Findings: Interobserver agreement was good (Î° = 0.6360), with 84% consensus of diagnoses during the first evaluation (21 of 25 cases). Kappa values increased to 0.6532 after reevaluation, and consensus was obtained in 24 (96%) of 25 cases. Overall intraobserver reproducibility was also good (Î° = 0.7824, ranging from 0.4991 to 1.000). Fewest changes in the classification were made in the FCD type II group (2.2% of 225 original diagnoses), whereas the majority of changes occurred in FCD type III (13.7% of 225 original diagnoses). In the third evaluation round, interobserver agreement was reflected by the level of experience of each neuropathologist, with Î° values ranging from moderate (0.5056; high level of experience >40 cases/year) to low (0.3265; low level of experience <10 cases/year). Significance: Our study achieved a good and reliable interobserver agreement among the group of expert neuropathologists originally involved in the ILAE FCD consensus classification system. Intraobserver reproducibility in this group was even more robust. These results showed considerable improvement compared to a previous study evaluating the 2004 Palmini FCD classification. Agreement levels were lower in our second group of neuropathologists and were related to their level of access and experience with epilepsy surgery specimens. These results suggested that the more precise ILAE definition of FCD histopathology patterns improves operational procedures in the diagnosis of FCDs. On the other hand, microscopic assessment of FCD is a challenge and requires sustained experience and teaching. The virtual slide review system allowed testing of this hypothesis and reached a widespread group of participating colleagues from different centers all over the world. We propose to further use this tool as a teaching device and also to address other epilepsy-associated entities still difficult to classify such as hippocampal sclerosis, long-term epilepsy-associated tumors, or mild malformations of cortical development (mMCDs), which were not yet covered by current ILAE classification systems. © 2012 International League Against Epilepsy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Agreement; Brain; Classification; Epilepsy; Neuropathology; Reproducibility

Hemispherotomy in children: A retrospective analysis of 152 surgeries at a single center and predictors for long-term seizure outcome - Kalbhenn, Thilo; Cloppenborg, Thomas; Woermann, Friedrich G.; Hagemann, Anne; Polster, Tilman; Coras, Roland; Blümcke, Ingmar; Bien, Christian G.; Simon, Matthias (Epilepsia, 2023)
Objective: Completeness as a predictor of seizure freedom is broadly accepted in epilepsy surgery. We focused on the requirements for a complete hemispherotomy and hypothesized that the disconnection of the insula contributes to a favorable postoperative seizure outcome. We analyzed surgical and nonsurgical predictors influencing long-term seizure outcome before and after a modification of our hemispherotomy technique. Methods: We retrospectively studied surgical procedures, electroclinical parameters, magnetic resonance imaging (MRI) results, and follow-up data in all children who had undergone hemispherotomy between 2001 and 2018 at our institution. We used logistic regression models to analyze the influence of different factors on seizure outcome. Results: A total of 152 patients were eligible for seizure outcome analysis only. Of these, 140 cases had complete follow-up data for ≥24 months and provide the basis for the following results. The median age at surgery was 4.3 years (range =.3–17.9 years). Complete disconnection (including the insular tissue) was achieved in 63.6% (89/140). At 2-year follow-up, seizure freedom (Engel class IA) was observed in 34.8% (8/23) with incomplete insular disconnection, whereas this was achieved in 88.8% (79/89) with complete surgical disconnection (p <.001, odds ratio [OR] = 10.41). In the latter group (n = 89), a potentially epileptogenic contralateral MRI lesion was the strongest predictor for postoperative seizure recurrence (OR = 22.20). Significance: Complete surgical disconnection is the most important predictor of seizure freedom following hemispherotomy and requires disconnection of the insular tissue at the basal ganglia level. Even if the hemispherotomy is performed surgically completely, a potentially epileptogenic contralateral lesion on preoperative MRI significantly reduces the chances of postoperative seizure freedom.
CRIS-Team Scopus Importer:2023-05-19
Keywords: completeness; disconnection; hemispherectomy; insular cortex

Herpes simplex virus encephalitis after temporal lobe resection: an infrequent but treatable complication of epilepsy surgery - Martínez-Poles, J.; Toledano, R.; Aledo-Serrano,; Korn, Klaus; Coras, Roland; Blümcke, Ingmar; García-Morales, I.; Álvarez-Linera, J.; Gil-Nagel, A. (European Journal of Neurology, 2020)
CRIS-Team Scopus Importer:2020-09-11
Keywords: clinical and diagnostic investigations; encephalitis; epilepsy; imaging; infections; magnetic resonance imaging (MRI); management; neurological disorders; surgery

Histological correlates of hippocampal magnetization transfer images in drug-resistant temporal lobe epilepsy patients - Peixoto-Santos, Jose Eduardo; Velasco, Tonicarlo R.; Carlotti, Carlos Gilberto; Assirati, Joao Alberto; Rezende, Gustavo Henrique de Souza e.; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Salmon, Carlos Ernesto Garrido; Santos, Antonio Carlos dos; Leite, Joao Pereira (NeuroImage: Clinical, 2020)
Objective: Temporal lobe epilepsy patients (TLE) often present with hippocampal atrophy, increased T2 relaxation, and reduced magnetization transfer ratio (MTR) in magnetic resonance images (MRI). The histological correlates of the reduced hippocampal MTR are so far unknown. Since MTR is dependent on the tissue's macromolecules, our aim was to evaluate the correlations between cellular populations, extracellular matrix molecules and the MTR in TLE patients. Methods: Patients with TLE (n = 26) and voluntaries (=20) were scanned in a 3 Tesla MRI scanner, and MTR images were calculated from 3DT1 sequences with magnetization pulse on resonance. Immunohistochemistry for neurons, reactive astrocytes, activated microglia, and extracellular matrix chondroitin sulfate were performed in formalin fixed, paraffin embedded tissues of TLE and autopsy controls (n = 10). Results were considered significant with adjusted p < 0.05. Results: Compared to the respective controls, TLE patients had reduced hippocampal MTR, increased reactive astrocytes and activated microglia, increased extracellular chondroitin sulfate, and reduced neuron density, compares to controls. MTR correlated positively with neuron density in CA3 and with chondroitin sulfate in CA3 and CA1. Multiple linear regressions reinforced the correlations between chondroitin sulfate and MTR. Significance: Our data indicate that extracellular matrix molecules are the most significant histological correlates of magnetization transfer ratio in the hippocampus of TLE patients.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Extracellular matrix; Hippocampal sclerosis; Magnetization transfer ratio; Neuron density; Temporal lobe epilepsy

Histopathological Features of Focal Cortical Dysplasia Type IIIc adjacent to Epilepsy-associated Vascular Malformations - Miyata, Hajime; Kuwashige, Haruka; Coras, Roland; Blümcke, Ingmar; Rossler, Karl; Kubota, Yuichi; Hori, Tomokatsu (JOURNAL OF NEUROPATHOLOGY AND EXPERIMENTAL NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Histopathology findings in MRI-negative focal epilepsy - Blümcke, Ingmar; Coras, Roland (Cambridge University Press, 2015)
Most surgically resected epileptogenic brain lesions are detectable by high-resolution MRI at 1.5 or 3 T, such as long-term epilepsy-associated tumors and hippocampal sclerosis of malformations of cortical development (MCD), and MRI visibility is a favorable predictor of postsurgical seizure control. However, recent studies suggest that comparable seizure control can be achieved after epilepsy surgery in patients with MRI-negative TLE, with 55% of patients remaining free of disabling seizures after a mean follow-up of 2 years [1] to 5.8 years [2]. In this chapter, we will discuss the spectrum of histopathological changes that can be observed in tissue specimens obtained from patients with MRI-negative focal epilepsy, with particular emphasis on the cellular architecture that hides such lesions from detection with currently available MRI protocols. However, neither the European Epilepsy Brain Bank nor the German Neuropathology Reference Center for Epilepsy Surgery allow us yet to reliably retrieve clinical information of how many operated patients were reported MRI negative. The increasing interest in this matter will help us to close this knowledge gap in the near future. MRI-negative FCDs The most prominent example for a structural brain abnormality identifiable in MRI-negative focal epilepsies may be focal cortical dysplasia (FCD) type IIa (Figure 19.1); FCDs represent a composite group of cortical malformations [3], which are increasingly recognized as a frequent morphological substrate for severe therapy-refractory epilepsy in children and young adults. However, not all FCD variants can be reliably detected by high-resolution MRI [4; 5]. The term FCD was originally coined by Taylor and colleagues in 1971 describing ten patients with microscopic evidence for dysmorphic neurons [6]. In half of these patients, the authors also described balloon cells. The current ILAE classification separate both variants into FCD type IIa (dysmorphic neurons, no balloon cells) and IIb (dysmorphic neurons and balloon cells) [3]. Yet, there is no distinguishing evidence for the clinical course, etiology and molecular-genetic or biological pathomechanisms of type IIa and IIb FCDs [5]. Furthermore, dysmorphic neurons are very similar between both variants and cannot be distinguished by morphometric analysis [7]. It is solely the presence of balloon cells, accompanied by lack of myelin and oligodendrocytes that makes the difference between the two subtypes of type II FCDs.
CRIS-Team Scopus Importer:2022-08-05

Human brain tissue with MOGHE carrying somatic SLC35A2 variants reveal aberrant protein expression and protein loss in the white matter - Cecchini, Erica; Geffers, Simon; Coras, Roland; Schultheis, Dorothea; Holtzhausen, Christian; Karandasheva, Kristina; Herrmann, Harald; Paulsen, Friedrich; Stadelmann, Christine; Kobow, Katja; Hartlieb, Till; Bien, Christian; et al. (Acta Neuropathologica, 2025)
Mild Malformation of Cortical Development with Oligodendroglial Hyperplasia in Epilepsy (MOGHE) is a recently described disease entity primarily affecting young children with drug-resistant epilepsy, mainly affecting the frontal lobe. The condition is histopathologically defined by focal lesions with patchy areas of increased oligodendroglial cell density at the grey-white matter boundary and heterotopic neurons in the white matter. Approximately half of the individuals with MOGHE carry brain somatic variants in the SLC35A2 gene, which affects the UDP-galactose transporter and thus sphingolipid glycosylation. To investigate the impact of SLC35A2 variants on protein expression, we analysed MOGHE brain tissue with and without SLC35A2 mosaicism, distinguishing missense from nonsense variants. We developed an antibody targeting the N-terminus of the SLC35A2 galactose transporter and applied it for immunofluorescence (IF) analyses in a MOGHE cohort comprising 59 genetically tested individuals selected from three centres in Germany. The cohort included 13 individuals with SLC35A2 missense variants and 15 with SLC35A2 nonsense variants. Our findings confirm the localisation of the SLC35A2 protein in the Golgi apparatus of all neuroepithelial cell types as well as within Golgi outposts along oligodendroglial processes. The protein distribution was altered in MOGHE samples dependent on the SLC35A2 variant and its allelic frequency. Western blot and IF analyses revealed a significant SLC35A2 reduction in MOGHE tissues carrying nonsense variants. Ultrastructural analyses from three MOGHE samples demonstrated hypomyelination in regions with increased oligodendroglial cell densities, regardless of the harbouring of SLC35A2 variants. Notably, this hypomyelination pattern decreased with age. These results suggested a role for the SLC35A2 protein in the pathogenesis of MOGHE and indicated the presence of additional myelin-associated pathomechanisms in those individuals who do not carry a pathogenic SLC35A2 varian
CRIS-Team Scopus Importer:2025-03-21
Keywords: MOGHE; Neuropathology; Brain; Myelin; Oligodendrocytes; Epilepsy

Increased expression of complement components in tuberous sclerosis complex and focal cortical dysplasia type 2B brain lesions - Gruber, Victoria-Elisabeth; Luinenburg, Mark J.; Colleselli, Katrin; Endmayr, Verena; Anink, Jasper J.; Zimmer, Till S.; Jansen, Floor; Gosselaar, Peter; Coras, Roland; Scholl, Theresa; Blümcke, Ingmar; Pimentel, Jose; et al. (Epilepsia, 2021)
Objective: Increasing evidence supports the contribution of inflammatory mechanisms to the neurological manifestations of epileptogenic developmental pathologies linked to mammalian target of rapamycin (mTOR) pathway dysregulation (mTORopathies), such as tuberous sclerosis complex (TSC) and focal cortical dysplasia (FCD). In this study, we aimed to investigate the expression pattern and cellular distribution of the complement factors C1q and C3 in resected cortical tissue of clinically well-characterized patients with TSC and FCD2B. Methods: We applied immunohistochemistry in TSC (n = 29) and FCD2B (n = 32) samples and compared them to autopsy and biopsy controls (n = 27). Furthermore, protein expression was observed via Western blot, and for descriptive colocalization studies immunofluorescence double labeling was performed. Results: Protein expression for C3 was significantly upregulated in TSC and FCD2B white and gray matter lesions compared to controls. Staining of the synaptic vesicle protein synaptophysin showed a remarkable increase in the white matter of both TSC and FCD2B. Furthermore, confocal imaging revealed colocalization of complement factors with astroglial, microglial, neuronal, and abnormal cells in various patterns. Significance: Our results demonstrate that the prominent activation of the complement pathway represents a common pathological hallmark of TSC and FCD2B, suggesting that complement overactivation may play a role in these mTORopathies.
CRIS-Team Scopus Importer:2021-12-24
Keywords: complement; cortical development; epilepsy; focal cortical dysplasia; inflammation; tuberous sclerosis complex

Integration of functional neuronavigation and intraoperative MRI in surgery for drug-resistant extratemporal epilepsy close to eloquent brain areas - Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard S.; Blümcke, Ingmar; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2013)
Object. The authors performed a retrospective study to assess the impact of functional neuronavigation and intraoperative MRI (iMRI) on surgery of extratemporal epileptogenic lesions on postsurgical morbidity and seizure control. Methods. Twenty-five patients (14 females and 11 males) underwent extratemporal resections for drug-resistant epilepsy close to speech/motor brain areas or adjacent to white matter tracts. The mean age at surgery was 34 years (range 12-67 years). The preoperative mean disease duration was 13.2 years. To avoid awake craniotomy, cortical motor-sensory representation was mapped during preoperative evaluation in 14 patients and speech representation was mapped in 15 patients using functional MRI. In addition, visualization of the pyramidal tract was performed in 11 patients, of the arcuate fascicle in 7 patients, and of the visual tract in 6 patients using diffusion tensor imaging. The mean minimum distance of tailored resection between the eloquent brain areas was 5.6mm. During surgery, blood oxygen level-dependent imaging and diffusion tensor imaging data were integrated into neuronavigation and displayed through the operating microscope. The postoperative mean follow-up was 44.2 months. Results. In 20% of these patients, further intraoperative resection was performed because of intraoperatively documented residual lesions according to iMRI findings. At the end of resection, the final iMRI scans confirmed achievement of total resection of the putative epileptogenic lesion in all patients. Postoperatively, transient complications and permanent complications were observed in 20% and 12% of patients, respectively. Favorable postoperative seizure control (Engel Classes I and II) was achieved in 84% and seizure freedom in 72% of these consecutive surgical patients. Conclusions. By using functional neuronavigation and iMRI for treatment of epileptogenic brain lesions, the authors achieved a maximum extent of resection despite the lesions' proximity to eloquent brain cortex and fiber tracts in all cases. The authors' results underline possible benefits of this technique leading to a favorable seizure outcome with acceptable neurological deficit rates in difficult-to-treat extratemporal epilepsy. © AANS, 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Eloquent brain area; Extratemporal epilepsy; Functional neuronavigation; Intraoperative MRI; Seizure outcome; Surgery

International consensus classification of hippocampal sclerosis in temporal lobe epilepsy: A Task Force report from the ILAE Commission on Diagnostic Methods - Blümcke, Ingmar; Thom, Maria; Aronica, Eleonora; Armstrong, Dawna D.; Bartolomei, Fabrice; Bernasconi, Andrea; Bernasconi, Neda; Bien, Christian G.; Cendes, Fernando; Coras, Roland; Cross, J. Helen; Jacques, Thomas S.; et al. (Epilepsia, 2013)
Hippocampal sclerosis (HS) is the most frequent histopathology encountered in patients with drug-resistant temporal lobe epilepsy (TLE). Over the past decades, various attempts have been made to classify specific patterns of hippocampal neuronal cell loss and correlate subtypes with postsurgical outcome. However, no international consensus about definitions and terminology has been achieved. A task force reviewed previous classification schemes and proposes a system based on semiquantitative hippocampal cell loss patterns that can be applied in any histopathology laboratory. Interobserver and intraobserver agreement studies reached consensus to classify three types in anatomically well-preserved hippocampal specimens: HS International League Against Epilepsy (ILAE) type 1 refers always to severe neuronal cell loss and gliosis predominantly in CA1 and CA4 regions, compared to CA1 predominant neuronal cell loss and gliosis (HS ILAE type 2), or CA4 predominant neuronal cell loss and gliosis (HS ILAE type 3). Surgical hippocampus specimens obtained from patients with TLE may also show normal content of neurons with reactive gliosis only (no-HS). HS ILAE type 1 is more often associated with a history of initial precipitating injuries before age 5 years, with early seizure onset, and favorable postsurgical seizure control. CA1 predominant HS ILAE type 2 and CA4 predominant HS ILAE type 3 have been studied less systematically so far, but some reports point to less favorable outcome, and to differences regarding epilepsy history, including age of seizure onset. The proposed international consensus classification will aid in the characterization of specific clinicopathologic syndromes, and explore variability in imaging and electrophysiology findings, and in postsurgical seizure control. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Epileptology; Hippocampus; Neurology; Neuropathology; Seizures

Intracerebral Hemorrhage-Associated Iron Release Leads to Pericyte-Dependent Cerebral Capillary Function Disruption. - Balk, Stefanie; Panier, Franziska; Brandner, Sebastian; Coras, Roland; Blümcke, Ingmar; Ekici, Arif Bülent; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen B.; Sprügel, Maximilian (Biomolecules, 2025)
Intracerebral hemorrhage leads to immediate brain injury due to local mechanical damage, on which current treatment approaches are focused, but it also induces secondary brain injury. The purpose of this study is to characterize blood components, degradation products and their effects in secondary brain injury. Immunocyto- and immunohistochemistry, Fluorescence-Activated Cell Sorting, WST-1 assays and RNA sequencing were applied using human cell cultures and human ex vivo brain tissue slices. Brain tissue was immediately collected, cooled and sliced during neurosurgical operations to perform experiments on living tissue slices of the human brain. Among the blood degradation products, free iron (Fe2+ and Fe3+), but not hemoglobin, induced detrimental effects on pericyte function and survival (78.5% vs. 94.3%; p-value < 0.001). RNA sequencing revealed ferroptosis as the underlining cellular mechanism, mediated via GPX-4 (log2 fold change > 1.0, p-value < 1.08 × 10-30) in pathway analysis and eventually resulting in oxidative cell death. Pericytes located at cerebral capillary branching sites were specifically affected by ferroptosis, leading to capillary disruption and vasoconstriction, which were partially prevented by ferrostatin-1. Free iron induces the pericyte-dependent disruption of cerebral capillary function and represents a therapeutic target to attenuate secondary injury after intracerebral hemorrhage.
EVALuna2:592285

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Meybohm, Patrick; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; et al. (Critical Care, 2022)
Background: In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed data from the German COVID-19 autopsy registry (DeRegCOVID). Methods: The electronic registry uses a web-based electronic case report form. In November 2021, the registry included N = 1129 confirmed COVID-19 autopsy cases, with data on 63 ECMO autopsy cases and 1066 non-ECMO autopsy cases, contributed from 29 German sites. Findings: The registry data showed that ECMO was used in younger male patients and bleeding events occurred much more frequently in ECMO cases compared to non-ECMO cases (56% and 9%, respectively). Similarly, intracranial bleeding (ICB) was documented in 21% of ECMO cases and 3% of non-ECMO cases and was classified as the immediate or underlying cause of death in 78% of ECMO cases and 37% of non-ECMO cases. In ECMO cases, the three most common immediate causes of death were multi-organ failure, ARDS and ICB, and in non-ECMO cases ARDS, multi-organ failure and pulmonary bacterial ± fungal superinfection, ordered by descending frequency. Interpretation: Our study suggests the potential value of autopsies and a joint interdisciplinary multicenter (national) approach in addressing fatal complications in COVID-19.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Autopsy; Bleeding events; COVID-19; ECMO; Intracranial bleeding; Registry

Isomorphic diffuse glioma is a morphologically and molecularly distinct tumour entity with recurrent gene fusions of MYBL1 or MYB and a benign disease course - Wefers, Annika K.; Stichel, Damian; Schrimpf, Daniel; Coras, Roland; Pages, Mélanie; Tauziède-Espariat, Arnault; Varlet, Pascale; Schwarz, Daniel; Söylemezoglu, Figen; Pohl, Ute; Pimentel, José; Meyer, Jochen; et al. (Acta Neuropathologica, 2019)
The “isomorphic subtype of diffuse astrocytoma” was identified histologically in 2004 as a supratentorial, highly differentiated glioma with low cellularity, low proliferation and focal diffuse brain infiltration. Patients typically had seizures since childhood and all were operated on as adults. To define the position of these lesions among brain tumours, we histologically, molecularly and clinically analysed 26 histologically prototypical isomorphic diffuse gliomas. Immunohistochemically, they were GFAP-positive, MAP2-, OLIG2- and CD34-negative, nuclear ATRX-expression was retained and proliferation was low. All 24 cases sequenced were IDH-wildtype. In cluster analyses of DNA methylation data, isomorphic diffuse gliomas formed a group clearly distinct from other glial/glio-neuronal brain tumours and normal hemispheric tissue, most closely related to paediatric MYB/MYBL1-altered diffuse astrocytomas and angiocentric gliomas. Half of the isomorphic diffuse gliomas had copy number alterations of MYBL1 or MYB (13/25, 52%). Gene fusions of MYBL1 or MYB with various gene partners were identified in 11/22 (50%) and were associated with an increased RNA-expression of the respective MYB-family gene. Integrating copy number alterations and available RNA sequencing data, 20/26 (77%) of isomorphic diffuse gliomas demonstrated MYBL1 (54%) or MYB (23%) alterations. Clinically, 89% of patients were seizure-free after surgery and all had a good outcome. In summary, we here define a distinct benign tumour class belonging to the family of MYB/MYBL1-altered gliomas. Isomorphic diffuse glioma occurs both in children and adults, has a concise morphology, frequent MYBL1 and MYB alterations and a specific DNA methylation profile. As an exclusively histological diagnosis may be very challenging and as paediatric MYB/MYBL1-altered diffuse astrocytomas may have the same gene fusions, we consider DNA methylation profiling very helpful for their identification.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Epilepsy; Gene fusion; Glioma; Isomorphic diffuse glioma; MYB; MYBL1

Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin

Lung cancer presenting with central nervous system metastasis: Clinicopathological and molecular analysis of 171 cases - Demleitner, Madeleine; Erlenbach-Wünsch, Katharina; Coras, Roland; Erber, Ramona; Polifka, Iris; Eyüpoglu, Ilker Yasin; Fuchs, Florian; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2023)
A subset of lung carcinoma presents initially with brain metastasis. Precise subtyping is mandatory for optimized treatment of these advanced aggressive carcinomas. We herein analyzed surgical biopsies from 171 Patients (99 males and 72 females aged 48–96; mean, 72), who presented with brain metastasis of lung cancer. In addition to conventional subtyping, we applied an extended immunohistochemistry (IHC) panel and performed several molecular tests looking for potential therapeutic targets other than EGFR mutations. Non-small cell carcinoma (NSCLC) comprised 157 (91.8 %) of cases: 109 (63.7 %) adenocarcinomas, 27 (15.8 %) squamous cell (SCC), 18 (10.5 %) large cell undifferentiated, 1 (0.6 %) adenosquamous and 2 (1.2 %) unclassified carcinomas. Of the adenocarcinomas, 81.7 % were TTF1+. Notably, 45 % of those TTF1-negative cases expressed HepPar1. SMARCA4 and SMARCA2 loss was observed in 13/171 (7.6 %) and 32/163 (19.6 %) cases, respectively; mainly TTF1- (40.0 %) and HepPar1+ (38.1 %) adenocarcinomas were affected by SMARCA2/4 loss. Loss of at least one mismatch repair (MMR) protein was observed in 3/156 (1.9 %) cases (2 adenocarcinomas and 1 large cell neuroendocrine carcinoma/LCNEC). Limited available data on mutation testing showed a frequency of EGFR mutations of 4.3% and of KRAS mutations of 57%. HER2 expression (2+/3+) was found in 45/166 (27.1 %) of cases with amplification verified by CISH in 18/38 (47.4 % of immunopositive cases and 10.5 % of the whole cohort); all but one were adenocarcinomas. Other genetic abnormalities detected included EML4::ALK rearrangements in 3 (1.8 %; 2 TTF1+ adenocarcinomas and 1 LCNEC) and RET rearrangements in one SCNEC. Variable subsets of tumors revealed amplifications of several potentially therapeutically targetable genes including MYC (30.0 %), MET (10.1 %), HER2 (10 %), FGFR1 (9.6 %), FGFR3 (4.6 %), and FGFR2 (3.4 %). This study highlights a highly heterogeneous molecular background in lung cancer presenting with CNS metastases. These findings highlight the need for individualized tumor testing strategies looking for potential therapeutic targets for this aggressive disease.
CRIS-Team Scopus Importer:2023-01-27
Keywords: ALK; Central nervous system metastasis; Immune therapy; Microsatellite instability; NSCLC; SMARCA4

MicroRNA519d and microRNA4758 can identify gangliogliomas from dysembryoplastic neuroepithelial tumours and astrocytomas. - Bongaarts, Anika; Prabowo, Avanita S.; Arena, Andrea; Anink, Jasper J.; Reinten, Roy J.; Jansen, Floor E.; Spliet, Wim G.M.; Thom, Maria; Coras, Roland; Blümcke, Ingmar; Kotulska, Katarzyna; Jozwiak, Sergiusz; et al. (Oncotarget, 2018)
Glioneuronal tumours, including gangliogliomas and dysembryoplastic neuroepithelial tumours, represent the most common low-grade epilepsy-associated brain tumours and are a well-recognized cause of intractable focal epilepsy in children and young adults. Classification is predominantly based on histological features, which is difficult due to the broad histological spectrum of these tumours. The aim of the present study was to find molecular markers that can be used to identify entities within the histopathology spectrum of glioneuronal tumours. The focus of this study was on microRNAs (miRNAs). miRNAs are important post-transcriptional regulators of gene expression and are involved in the pathogenesis of different neurological diseases and oncogenesis. Using a miRNA array, miR-519d and miR-4758 were found to be upregulated in gangliogliomas (n=26) compared to control cortex (n=17), peritumoural tissue (n=7), dysembryoplastic neuroepithelial tumours (n=9) and astrocytomas (grade I-IV; subependymal giant cell astrocytomas, n=10; pilocytic astrocytoma, n=15; diffuse astrocytoma grade II, n=10; grade III, n=14 and glioblastoma n=15). Furthermore, the PI3K/AKT3/P21 pathway, which is predicated to be targeted by miR-519d and miR-4758, was deregulated in gangliogliomas. Functionally, overexpression of miR-519d in an astrocytic cell line resulted in a downregulation of CDKN1A (P21) and an increase in cell proliferation, whereas co-transfection with miR-4758 counteracted this effect. These results suggest that miR-519d and miR-4758 might work in concert as regulators of the cell cycle in low grade gliomas. Furthermore, these miRNAs could be used to distinguish gangliogliomas from dysembryoplastic neuroepithelial tumours and other low and high grade gliomas and may lead to more targeted therapy.
EVALuna2:417091

Mild malformation of cortical development with oligodendroglial hyperplasia in frontal lobe epilepsy (MOGHE): a report of the first case in Bulgaria. - Metodiev, Dimitar; Minkin, Krassimir; Dimova, Petia; Blümcke, Ingmar; Coras, Roland; Ruseva, Margarita; Ganeva, Rumiana; Parvanov, Dimitar; Penkov, Marin; Nachev, Sevdalin (Folia Neuropathologica, 2025)
Herein, we report the first case of mild malformation of cortical development with oligodendroglial hyperplasia and epilepsy (MOGHE) in Bulgaria. It is a newly recognised clinico-pathological entity with medically intractable focal epilepsy in paediatric patients. The patient of interest is a 9-year-old boy who has been suffering from refractory epilepsy since the age of three. Positron emission tomography revealed a consistent hypometabolism with maximum in the orbitofrontal and fronto-opercular cortex, as well as in the adjacent anterior insula and the anterior temporal regions. A left frontal corticotomy anterior from the precentral sulcus, left insulectomy and temporal disconnection were performed. Pathomorphological examination of the material from the resected brain tissues demonstrated oligodendroglial hyperplasia with blurring of grey-white-matter boundaries and presence of subcortical heterotopic neurones. Eighteen months post-surgically the patient is seizure-free and drug-free. The observed oligodendroglial hyperplasia with increased proliferative activity and heterotopic neurones in the white matter with blurring of grey-white-matter junctions are the histopathological hallmarks of MOGHE. More new cases are needed to establish further data about this distinct entity in frontal lobe epilepsy.
EVALuna2:592282

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

Multilobar unilateral hypoplasia with emphasis on the posterior quadrant and severe epilepsy in children with FCD ILAE Type 1A - Holthausen, Hans; Coras, Roland; Tang, Yingying; Bai, Lily; Wang, Irene; Pieper, Tom; Kudernatsch, Manfred; Hartlieb, Till; Staudt, Martin; Winkler, Peter; Hofer, Wiebke; Jabari, Samir; et al. (Epilepsia, 2021)
Objective: Focal cortical dysplasia (FCD) Type 1 and its three subtypes have yet not been fully characterized at the clinical, anatomopathological, and molecular level (International League Against Epilepsy [ILAE] FCD classification from 2011). We aimed to describe the clinical phenotype of patients with histopathologically confirmed FCD1A obtained from a single epilepsy center between 2002 and 2016. Methods: Medical records were retrieved from the hospital's archive. Results from electroencephalography (EEG) video recordings, neuroimaging, and histopathology were reevaluated. Magnetic resonance imaging (MRI) post-processing was retrospectively performed in nine patients. DNA methylation studies were carried out from archival surgical brain tissue in 11 patients. Results: Nineteen children with a histopathological diagnosis of FCD1A were included. The average onset of epilepsy was 0.9 years (range 0.2–10 years). All children had severe cognitive impairment and one third had mild motor deficits, yet fine finger movements were preserved in all patients. All patients had daily seizures, being drug resistant from disease onset. Interictal electroencephalography revealed bilateral multi-regional epileptiform discharges. Interictal status epilepticus was observed in 8 and countless subclinical seizures in 11 patients. Regional continuous irregular slow waves were of higher lateralizing and localizing yield than spikes. Posterior background rhythms were normal in 16 of 19 children. Neuroimaging showed unilateral multilobar hypoplasia and increased T2-FLAIR signals of the white matter in 18 of 19 patients. All children underwent tailored multilobar resections, with seizure freedom achieved in 47% (Engel class I). There was no case with frontal involvement without involvement of the posterior quadrant by MRI and histopathology. DNA methylation profiling distinguished FCD1A samples from all other epilepsy specimens and controls. Significance: We identified a cohort of young children with drug resistance from seizure onset, bad EEG with posterior emphasis, lack of any focal neurological deficits but severe cognitive impairment, subtle hypoplasia of the epileptogenic area on MRI, and histopathologically defined and molecularly confirmed by DNA methylation analysis as FCD ILAE Type 1A.
CRIS-Team Scopus Importer:2021-11-12
Keywords: brain; neuroimaging; neuropathology; neurophysiology; seizure

Myelin Pathology Beyond White Matter in Tuberous Sclerosis Complex (TSC) Cortical Tubers - Mühlebner, Angelika; Van Scheppingen, Jackelien; De Neef, Andrew; Bongaarts, Anika; Zimmer, Till S.; Mills, James D.; Jansen, Floor E.; Spliet, Wim G.M.; Krsek, Pavel; Zamecnik, Josef; Coras, Roland; Blümcke, Ingmar; et al. (Journal of Neuropathology and Experimental Neurology, 2020)
Tuberous sclerosis complex (TSC) is a monogenetic disease that arises due to mutations in either the TSC1 or TSC2 gene and affects multiple organ systems. One of the hallmark manifestations of TSC are cortical malformations referred to as cortical tubers. These tubers are frequently associated with treatment-resistant epilepsy. Some of these patients are candidates for epilepsy surgery. White matter abnormalities, such as loss of myelin and oligodendroglia, have been described in a small subset of resected tubers but mechanisms underlying this phenomenon are unclear. Herein, we analyzed a variety of neuropathologic and immunohistochemical features in gray and white matter areas of resected cortical tubers from 46 TSC patients using semi-automated quantitative image analysis. We observed divergent amounts of myelin basic protein as well as numbers of oligodendroglia in both gray and white matter when compared with matched controls. Analyses of clinical data indicated that reduced numbers of oligodendroglia were associated with lower numbers on the intelligence quotient scale and that lower amounts of myelin-associated oligodendrocyte basic protein were associated with the presence of autism-spectrum disorder. In conclusion, myelin pathology in cortical tubers extends beyond the white matter and may be linked to cognitive dysfunction in TSC patients.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Cognitive dysfunction; Epilepsy; Myelin; Tuberous sclerosis complex; White matter

N471D WASH complex subunit strumpellin knock-in mice display mild motor and cardiac abnormalities and BPTF and KLHL11 dysregulation in brain tissue - Clemen, Christoph S.; Schmidt, Andreas; Winter, Lilli; Canneva, Fabio; Wittig, Ilka; Becker, Lore; Coras, Roland; Berwanger, Carolin; Hofmann, Andreas; Eggers, Britta; Marcus, Katrin; Gailus-Durner, Valerie; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims We investigated N471D WASH complex subunit strumpellin (Washc5) knock-in and Washc5 knock-out mice as models for hereditary spastic paraplegia type 8 (SPG8). Methods We generated heterozygous and homozygous N471D Washc5 knock-in mice and subjected them to a comprehensive clinical, morphological and laboratory parameter screen, and gait analyses. Brain tissue was used for proteomic analysis. Furthermore, we generated heterozygous Washc5 knock-out mice. WASH complex subunit strumpellin expression was determined by qPCR and immunoblotting. Results Homozygous N471D Washc5 knock-in mice showed mild dilated cardiomyopathy, decreased acoustic startle reactivity, thinner eye lenses, increased alkaline phosphatase and potassium levels and increased white blood cell counts. Gait analyses revealed multiple aberrations indicative of locomotor instability. Similarly, the clinical chemistry, haematology and gait parameters of heterozygous mice also deviated from the values expected for healthy animals, albeit to a lesser extent. Proteomic analysis of brain tissue depicted consistent upregulation of BPTF and downregulation of KLHL11 in heterozygous and homozygous knock-in mice. WASHC5-related protein interaction partners and complexes showed no change in abundancies. Heterozygous Washc5 knock-out mice showing normal WASHC5 levels could not be bred to homozygosity. Conclusions While biallelic ablation of Washc5 was prenatally lethal, expression of N471D mutated WASHC5 led to several mild clinical and laboratory parameter abnormalities, but not to a typical SPG8 phenotype. The consistent upregulation of BPTF and downregulation of KLHL11 suggest mechanistic links between the expression of N471D mutated WASHC5 and the roles of both proteins in neurodegeneration and protein quality control, respectively.
CRIS-Team WoS Importer:2021-08-27

Neuroinflammatory disease signatures in SPG11-related hereditary spastic paraplegia patients. - Krumm, Laura; Pozner, Tatyana; Zagha, Naime; Coras, Roland; Arnold, Philipp; Tsaktanis, Thanos; Scherpelz, Kathryn; Davis, Marie Y.; Kaindl, Johanna; Stolzer, Iris; Süß, Patrick; Khundadze, Mukhran; et al. (Acta Neuropathologica, 2024)
Biallelic loss of SPG11 function constitutes the most frequent cause of complicated autosomal recessive hereditary spastic paraplegia (HSP) with thin corpus callosum, resulting in progressive multisystem neurodegeneration. While the impact of neuroinflammation is an emerging and potentially treatable aspect in neurodegenerative diseases and leukodystrophies, the role of immune cells in SPG11-HSP patients is unknown. Here, we performed a comprehensive immunological characterization of SPG11-HSP, including examination of three human postmortem brain donations, immunophenotyping of patients' peripheral blood cells and patient-specific induced pluripotent stem cell-derived microglia-like cells (iMGL). We delineate a previously unknown role of innate immunity in SPG11-HSP. Neuropathological analysis of SPG11-HSP patient brain tissue revealed profound microgliosis in areas of neurodegeneration, downregulation of homeostatic microglial markers and cell-intrinsic accumulation of lipids and lipofuscin in IBA1+ cells. In a larger cohort of SPG11-HSP patients, the ratio of peripheral classical and intermediate monocytes was increased, along with increased serum levels of IL-6 that correlated with disease severity. Stimulation of patient-specific iMGLs with IFNγ led to increased phagocytic activity compared to control iMGL as well as increased upregulation and release of proinflammatory cytokines and chemokines, such as CXCL10. On a molecular basis, we identified increased STAT1 phosphorylation as mechanism connecting IFNγ-mediated immune hyperactivation and SPG11 loss of function. STAT1 expression was increased both in human postmortem brain tissue and in an Spg11-/- mouse model. Application of an STAT1 inhibitor decreased CXCL10 production in SPG11 iMGL and rescued their toxic effect on SPG11 neurons. Our data establish neuroinflammation as a novel disease mechanism in SPG11-HSP patients and constitute the first description of myeloid cell/ microglia activation in human SPG11-HSP. IFNγ/ STAT1-mediated neurotoxic effects of hyperreactive microglia upon SPG11 loss of function indicate that immunomodulation strategies may slow down disease progression.
EVALuna2:552646

Neuropathologic measurements in focal cortical dysplasias: validation of the ILAE 2011 classification system and diagnostic implications for MRI - Mühlebner, Angelika; Coras, Roland; Kobow, Katja; Feucht, Martha; Czech, Thomas; Stefan, Hermann; Buchfelder, Michael; Holthausen, Hans; Kudernatsch, Manfred; Blümcke, Ingmar; et al. (Acta Neuropathologica, 2012)
Focal cortical dysplasias (FCD) which represent a composite group of cortical malformations are increasingly recognized as morphological substrate for severe therapy-refractory epilepsy in children and young adults. However, presurgical evaluation remains challenging as not all FCD variants can be reliably detected by high-resolution magnetic resonance imaging (MRI). Here, we studied a cohort of 52 epilepsy patients with neuropathological evidence for FCD using the 2011 classification of the International League against Epilepsy (ILAE) and systematically analysed those histopathologic features applicable also for MRI diagnostics. Histopathologic parameters included quantitative measurements of cellular profiles, cortical thickness, heterotopic neurons in white matter, and myelination that were compared between FCD subtypes and age-/localization-matched controls (n = 36) using multivariate analysis. Dysmorphic neurons in both FCD Type II variants showed significantly increased diameter of their cell bodies and nuclei. Cortical thickness was also increased with a distinct loss of myelin content specifying FCD Type IIb from IIa. The data further suggested that myelination deficits in FCD Type IIb result from compromised oligodendroglial lineage differentiation and we concluded that the "transmantle sign" is a unique finding in FCD Type IIb. In contrast, FCD Type Ia was characterized by a smaller cortical ribbon and higher neuronal densities, but these parameters failed to reach statistical significance (considering age-and location-dependent variability in controls). All FCD variants showed abnormal grey-white matter boundaries with increased numbers of heterotopic neurons. Similar results were obtained also at deep white matter location. Thus, many FCD variants may indeed escape visual MRI inspection, but suspicious areas with increased or decreased cortical thickness as well as grey-white matter blurring may be uncovered using post-processing protocols of neuroimaging data. The systematic analysis of well-specified histopathological features could be helpful to improve sensitivity and specificity in MRI detection during pre-surgical work-up of patients with drug-resistant focal epilepsies.
Keywords: Malformations; Neocortex; MRI; Seizures; Epilepsy; Neuropathology

Neuroprotective intervention by interferon-γ blockade prevents CD8+ T cell-mediated dendrite and synapse loss - Kreutzfeldt, Mario; Bergthaler, Andreas; Fernandez, Marylise; Brueck, Wolfgang; Steinbach, Karin; Vorm, Mariann; Coras, Roland; Blümcke, Ingmar; Bonilla, Weldy V.; Fleige, Anne; Forman, Ruth; Mueller, Werner; et al. (Journal of Experimental Medicine, 2013)
Neurons are postmitotic and thus irreplaceable cells of the central nervous system (CNS). Accordingly, CNS inflammation with resulting neuronal damage can have devastating consequences. We investigated molecular mediators and structural consequences of CD8+ T lymphocyte (CTL) attack on neurons in vivo. In a viral encephalitis model in mice, disease depended on CTL-derived interferon-γ (IFN-γ) and neuronal IFN-γ signaling. Downstream STAT1 phosphorylation and nuclear translocation in neurons were associated with dendrite and synapse loss (deafferentation). Analogous molecular and structural alterations were also found in human Rasmussen encephalitis, a CTL-mediated human autoimmune disorder of the CNS. Importantly, therapeutic intervention by IFN-γ blocking antibody prevented neuronal deafferentation and clinical disease without reducing CTL responses or CNS infiltration. These findings identify neuronal IFN-γ signaling as a novel target for neuroprotective interventions in CTL-mediated CNS disease. © 2013 Kreutzfeldt et al.
CRIS-Team Scopus Importer:2022-08-05

Operative variations in temporal lobe epilepsy surgery and seizure and memory outcome in 226 patients suffering from hippocampal sclerosis - Rössler, Karl; Kasper, Burkhard; Shawarba, Julia; Walther, Katrin; Coras, Roland; Brandner, Sebastian; Winter, Fabian; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (Neurological Research, 2021)
Objective: The aim of this retrospective cohort study was to assess seizure and memory outcomes following temporal lobe surgery in patients suffering from medically refractory temporal lobe epilepsy (TLE) and hippocampal sclerosis (HS). Methods: A retrospective monocentric data analysis was performed in consecutive patients who were operated on during 2002–2018. In the first decennium, standard temporal lobe resections (TLR) were predominately performed, and later, antero-temporal lobe resections (ATLR) were mainly performed. Seizure and memory outcomes over time were assessed according to ILAE/Engel classification and the Berlin Amnesia Test (BTA), respectively. Results: Altogether, 231 surgeries were performed on 226 patients (mean age, 40 years [range, 10–68 years]; male: female, 1:1.4; mean seizure duration, 25 years; and mean follow-up duration, 4.75 years [range, 1–16]). Recently, outcomes of 78.3% of the patients in the total cohort were classified as Engel class I, with 54.9% of patients being completely seizure free. The recent cohort of ATLR since 2012 showed significant more completely seizure-free patients than before 2012 (Engel IA 46.6% versus 67.7%, p < 0.0025, χ 2), although the Kaplan Meier analysis of all patients favors TLR for better seizure outcome (61% ATLR vs 73% TLR seizure free after 5 yrs, log rank p < 0.001). Verbal memory improved significantly in non-dominant patients. Minor neurological complications were noted (permanent severe complications, 0.4%; temporary severe complications, 4.8%). Conclusion: Significant improvements in seizure and memory outcomes were observed over time, with surgical technique and seizure duration as important prognostic factors. Early admittance for surgery may favor an excellent seizure outcome in patients undergoing temporal lobe resection for HS.
CRIS-Team Scopus Importer:2021-07-02
Keywords: amygdalo-hippocampectomy; antero-temporal resection; Hippocampal sclerosis; seizure outcome; standard temporal lobe resection; temporal lobe epilepsy

Outcome of Epilepsy Surgery in MRI-Negative Patients Without Histopathologic Abnormalities in the Resected Tissue - Sanders, Maurits W.; Van Der Wolf, Iskander; Jansen, Floor E.; Aronica, Eleonora; Helmstaedter, Christoph; Racz, Attila; Surges, Rainer; Grote, Alexander; Becker, Albert J.; Rheims, Sylvain; Catenoix, Hélène; Duncan, John S.; et al. (Neurology, 2024)
Background and Objective Patients with presumed nonlesional focal epilepsy - based on either MRI or histopathologic findings - have a lower success rate of epilepsy surgery compared with lesional patients. In this study, we aimed to characterize a large group of patients with focal epilepsy who underwent epilepsy surgery despite a normal MRI and had no lesion on histopathology. Determinants of their postoperative seizure outcomes were further studied. Methods We designed an observational multicenter cohort study of MRI-negative and histopathology-negative patients who were derived from the European Epilepsy Brain Bank and underwent epilepsy surgery between 2000 and 2012 in 34 epilepsy surgery centers within Europe. We collected data on clinical characteristics, presurgical assessment, including genetic testing, surgery characteristics, postoperative outcome, and treatment regimen. Results Of the 217 included patients, 40% were seizure-free (Engel I) 2 years after surgery and one-third of patients remained seizure-free after 5 years. Temporal lobe surgery (adjusted odds ratio [AOR]: 2.62; 95% CI 1.19-5.76), shorter epilepsy duration (AOR for duration: 0.94; 95% CI 0.89-0.99), and completely normal histopathologic findings - versus nonspecific reactive gliosis - (AOR: 4.69; 95% CI 1.79-11.27) were significantly associated with favorable seizure outcome at 2 years after surgery. Of patients who underwent invasive monitoring, only 35% reached seizure freedom at 2 years. Patients with parietal lobe resections had lowest seizure freedom rates (12.5%). Among temporal lobe surgery patients, there was a trend toward favorable outcome if hippocampectomy was part of the resection strategy (OR: 2.94; 95% CI 0.98-8.80). Genetic testing was only sporadically performed. Discussion This study shows that seizure freedom can be reached in 40% of nonlesional patients with both normal MRI and histopathology findings. In particular, nonlesional temporal lobe epilepsy should be regarded as a relatively favorable group, with almost half of patients achieving seizure freedom at 2 years after surgery - even more if the hippocampus is resected - compared with only 1 in 5 nonlesional patients who underwent extratemporal surgery. Patients with an electroclinically identified focus, who are nonlesional, will be a promising group for advanced molecular-genetic analysis of brain tissue specimens to identify new brain somatic epilepsy genes or epilepsy-associated molecular pathways.
CRIS-Team Scopus Importer:2024-10-04

Papillary tumor of the pineal region with anaplastic small cell component - Heim, Stephanie; Coras, Roland; Ganslandt, Oliver; Kufeld, Markus; Blümcke, Ingmar; Paulus, Werner; Hasselblatt, Martin (Journal of Neuro-Oncology, 2013)
CRIS-Team Scopus Importer:2022-08-05

Patterns of phosphorylated tau accumulation in a spectrum of acquired and developmental brain lesions associated with refractory epilepsy - Mrzyglod, Alicja; Mebrouk, Anya; Bartkiewicz, Joanna; El Hachami, Hanaa; Ryniejska, Maritchka; de Tisi, Jane; Coras, Roland; Blümcke, Ingmar; Xiao, Fenglai; Miserocchi, Anna; McEvoy, Andrew; Koepp, Matthias; et al. (Epilepsia, 2025)
Objective: Phosphorylated tau (pTau) has been reported in surgical resections in refractory epilepsy. It is unclear whether this is activity-driven physiological pTau or signifies the advent of neurodegenerative cascades, relevant to memory decline. To date, primarily hippocampal sclerosis and focal cortical dysplasia (FCD) type II have been studied. We aimed to explore pTau in a range of acquired and developmental epileptogenic pathologies to assess its prevalence and identify potential drivers. Method: A total of 104 cases were studied representing FCD IA (n = 11), FCD IIIA (n = 5), FCD IIIB (n = 6), cavernoma (n = 11), Sturge–Weber leptomeningeal angiomatosis (n = 10), meningioangiomatosis (n = 4), perinatal infarcts (n = 9), Rasmussen encephalitis (RE; n = 6), gray matter heterotopia (n = 6), old scars (n = 10), and temporal lobe encephaloceles (n = 7); we also included focal microinjuries following prior stereoelectroencephalography at different ages (n = 19; four in lesion-negative cases). pTau was evaluated with AT8 immunohistochemistry, with further multiplex panels of AT8 with other established pTau markers (AT100, AT180, PHF1, CP13), pS6, glial fibrillary acidic protein, reelin, calbindin, and Tbr1 in selected cases. Labeling in the lesion was compared with adjacent cortex and clinical factors such as epilepsy duration. Results: pTau was identified in low to moderate levels in 60% overall, mainly localized to the epileptogenic lesion and more frequent in vascular malformations (74%–100%). pTau was noted in the superficial cortex across pathologies including encephaloceles, associated with superficial gliosis. In perinatal infarcts, distinct pTau patterns were noted in the superficial ulegyric cortex and heterotopic neuronal islands. Glial pTau was rare, and FCD IA, FCD IIIA/B, and microinjuries were negative. Variable regional expression of AT8 and mTOR activation markers (pS6) was noted, including in one RE case. Higher pTau expression was associated with older age at surgery and at onset of epilepsy, suggesting additional age-related vulnerability. Significance: Our findings highlight localized and distinct patterns of pTau in some epilepsy pathologies. Plausible pathomechanisms include local vascular insufficiency, neuronal dysmaturation, and aging as well as seizure activity and provide direction for future exploration.
CRIS-Team Scopus Importer:2025-05-16
Keywords: acquired scar; developmental; focal epilepsy; tau

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Phase-amplitude coupling measures for determination of the epileptic network: A methodological comparison - Ali, Ryshum; Gollwitzer, Stephanie; Reindl, Caroline; Hamer, Hajo; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael; Hastreiter, Peter; Rampp, Stefan (Journal of Neuroscience Methods, 2022)
CRIS-Team WoS Importer:2022-05-13
Keywords: EEG; Epilepsy; Phase-Amplitude Coupling

PLEKHG5 regulates autophagy, survival and MGMT expression in U251-MG glioblastoma cells - Witte, Kaya Elisa; Slotta, Carsten; Luetkemeyer, Melanie; Kitke, Angelika; Coras, Roland; Simon, Matthias; Kaltschmidt, Christian; Kaltschmidt, Barbara (Scientific Reports, 2020)
A signalling pathway involving PLEKHG5 (guanine exchange factor) for the Ras superfamily member RAB26 to transcription factor NF-kappa B was discovered in autophagy. PLEKHG5 was reported in glioblastoma multiforme (GBM) and correlates with patient survival. Thus, the generation of a cellular model for understanding PLEKHG5 signalling is the study purpose. We generated a CRISPR/Cas9-mediated knockout of PLEKHG5 in U251-MG glioblastoma cells and analysed resulting changes. Next, we used a mRFP-GFP-LC3(+) reporter for visualisation of autophagic defects and rescued the phenotype of PLEKHG5 wildtype via transduction of a constitutively active RAB26QL-plasmid. Effects of overexpressing RAB26 were investigated and correlated with the O-6-methylguanine-DNA methyltransferase (MGMT) and cellular survival. PLEKHG5 knockout showed changes in morphology, loss of filopodia and higher population doubling times. Accumulation of autolysosomes was resulted by decreased LAMP-1 in PLEKHG5-deficient cells. Rescue of PLEKHG5(-/-) restored the downregulation of RhoA activity, showed faster response to tumour necrosis factor and better cellular fitness. MGMT expression was activated after RAB26 overexpression compared to non-transduced cells. Survival of PLEKHG5 knockout was rescued together with sensitivity to temozolomide by RAB26QL. This study provides new insights in the PLEKHG5/RAB26 signalling within U251-MG cells, which suggests potential therapeutic strategies in other glioma cells and further in primary GBM.
CRIS-Team WoS Importer:2021-01-15

Reirradiation of recurent glioblastomas: High prognostic significance of contrast-enhancing tumor volume - Mansoorian, Sina; Coras, Roland; Weissmann, Thomas; Lettmaier, Sebastian; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Schmidt, M.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Role of NODDI in the MRI Characterization of Hippocampal Abnormalities in Temporal Lobe Epilepsy Clinico-histopathologic Correlations - Giachetti, Isabella; Padelli, Francesco; Aquino, Domenico; Garbelli, Rita; De Santis, Dalia; Rossini, Laura; Deleo, Francesco; Pascuzzo, Riccardo; Coras, Roland; Marucci, Gianluca; Tringali, Giovanni; Maccagnano, Carmelo; et al. (Neurology, 2022)
Background and Objectives The identification of possible hippocampal alterations is a crucial point for the diagnosis and therapy of patients with unilateral temporal lobe epilepsy (TLE). This study aims to investigate the role of neurite orientation dispersion and density imaging (NODDI) compared to diffusion tensor imaging (DTI) in the comprehension of hippocampal microstructure in TLE. Methods DTI and NODDI metrics were calculated in the hippocampi of adult patients with TLE, with and without histology-confirmed hippocampal sclerosis (HS), and in age/sex-matched healthy controls (HC). Diffusion metrics and hippocampal volumes of the pathologic side were compared within participants and between participants among the HS, non-HS, and HC groups. Diffusion metrics were also correlated with hippocampal volume and patients' clinical features. After surgery, hippocampal specimens were processed for neuropathology examinations. Results Fifteen patients with TLE (9 with and 6 without HS) and 11 HC were included. Hippocampal analyses resulted in a significant increase in fractional anisotropy (FA) and mean diffusivity (MD; mm(2)/s x 10(-3)) and decrease in orientation dispersion index (ODI) comparing the pathologic side of patients with HS and their relative nonpathologic side (0.203 vs 0.183, 0.825 vs 0.724, 0.366 vs 0.443, respectively), the pathologic side of patients without HS (0.203 vs 0.169, 0.825 vs 0.745, 0.366 vs 0.453, respectively), and HC (0.203 vs 0.172, 0.825 vs 0.729, 0.366 vs 0.447, respectively). Moreover, neurite density (ND) was significantly decreased comparing both hippocampi of patients with HS (0.416 vs 0.460). A significant increase in free-water isotropic volume fraction (fiso) was found in the comparison of pathologic hippocampi of patients with HS and nonpathologic hippocampi of patients with HS (0.323 vs 0.258) and HC (0.323 vs 0.226). Hippocampal volume of all patients with TLE negatively correlated with MD (r = -0.746, p = 0.0145) and positively correlated with ODI (r = 0.719, p = 0.0145). Fiso and ND of sclerotic hippocampi positively correlated with disease duration (r = 0.684, p = 0.0424 and r = 0.670, p = 0.0486, respectively). Immunohistochemistry in sclerotic hippocampal specimens revealed neuronal loss in the pyramidal layer and fiber reorganization at the level of stratum lacunosum-moleculare, confirming ODI and ND metrics. Discussion This study shows the capability of diffusion MRI metrics to detect hippocampal microstructural alterations. Among them, ODI seems to better highlight the fiber reorganization observed by neuropathology in sclerotic hippocampi.
CRIS-Team WoS Importer:2022-05-13

Seizure outcomes following epilepsy surgery in pediatric and young adult patients with high-grade brain tumors: Results from a European survey - Lersch, Robert; Hartlieb, Till; Pieper, Tom; Kudernatsch, Manfred; Hofer, Wiebke; Barba, Carmen; Guerrini, Renzo; Giordano, Flavio; Pommella, Marianna; Schubert-Bast, Susanne; Syrbe, Steffen; Rego, Ricardo; et al. (Epilepsia, 2025)
Objective: Epilepsy surgery is a standard treatment for drug-resistant epilepsy, resulting in seizure freedom in a significant number of cases. Although frequently performed for low-grade brain tumors, it is rarely considered for high-grade tumors, despite the impact of chronic epilepsy on quality of life and cognition. Methods: This retrospective multicenter study across 43 European centers evaluated epilepsy surgery outcomes in children with high-grade brain tumors (World Health Organization grades III and IV). Two cohorts of patients younger than 25 years were studied: (1) those undergoing epilepsy surgery after tumor resection (n = 14) and (2) those initially suspected of low-grade lesions but diagnosed with high-grade brain tumors postsurgery (n = 11). Results: Eighty percent of patients achieved seizure freedom 1 year after last epilepsy surgery: 71% in Cohort 1 and 91% in Cohort 2. Eighty-four percent were free of disabling seizures (Engel IA–D) after a median follow-up period of 4.3 years (range = 1–15.9 years). No surgery-related deaths occurred. Thirty-two percent of children experienced persistent morbidity, including motor dysfunction, visual impairment, persistent seizures, cognitive deficits, and hydrocephalus. Significance: Epilepsy surgery is effective for medically refractory epilepsy in children with high-grade central nervous system tumors and should be considered early, as seizure freedom is achieved in the majority of patients. Despite involving numerous epilepsy centers, only 25 patients were recruited, indicating that this method is rarely considered for high-grade brain tumor patients with medically refractory epilepsy.
CRIS-Team Scopus Importer:2025-03-14
Keywords: children; drug-resistant epilepsy; epilepsy surgery; high-grade brain tumors; seizure freedom

Skull Base Chordomas and Chondrosarcomas - Kremenevski, Natalia; Schlaffer, Sven-Martin; Coras, Roland; Kinfe, Thomas Mehari; Graillon, Thomas; Buchfelder, Michael (Neuroendocrinology, 2020)
Skull base chordomas account for less than 0.2% and chondrosarcomas for less than 0.15% of all intracranial tumors. Although their clinical and imaging presentations are similar, they derive from different origins. Chordomas arise from embryonic remnants of the primitive notochord and chondrosarcomas from primitive mesenchymal cells or from the embryonic rest of the cranial cartilaginous matrix. Both entities are characterized by infiltration and destruction of the surrounding bone and soft tissue and a high locoregional recurrence rate. Chondrosarcomas, when treated with similar complex strategies, display a much better prognosis than chordomas. The overall survival is approximately 65% for chordomas and 80% for chondrosarcomas at 5 years and 30 and 50%, respectively, at 10 years. Chordomas are divided into the following 3 histological types: classical (conventional), chondroid, and dedifferentiated. Chondrosarcomas have conventional, mesenchymal, clear cell, and dedifferentiated subgroups. Both tumor entities often present with nonspecific symptoms, and headaches are the most reported initial symptom. Computed tomography and magnetic resonance imaging are required to determine the tumor localization and the extent of tumor growth. The treatment philosophy is to maximize tumor resection, minimize morbidity, and preserve function. Neurosurgical approaches commonly used for the resection of intracranial chordomas and chondrosarcomas are transsphenoidal, transbasal, cranio-orbitozygomatic, transzygomatic extended middle fossa, transcondylar, and transmaxillary approaches. Chordomas and chondrosarcomas are not sensitive to chemotherapy and there are no approved drugs for their treatment. The present treatment concept is a combination of surgical resection with a maximal excision and preserving patients' quality of life by adjuvant radiotherapy for both chordomas and chondrosarcomas.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chondrosarcoma; Chordoma; Diagnosis; Skull base; Therapy

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Stereotactic depth electrode placement surgery in paediatric and adult patients with the Neuromate robotic device: Accuracy, complications and epileptological results - Kalbhenn, Thilo; Cloppenborg, Thomas; Coras, Roland; Fauser, Susanne; Hagemann, Anne; Omaimen, Hassan; Polster, Tilman; Yasin, Hamzah; Woermann, Friedrich G.; Bien, Christian G.; Simon, Matthias (Seizure-European Journal of Epilepsy, 2021)
Objective: The number of patients requiring depth electrode implantation for invasive video EEG diagnostics increases in most epilepsy centres. Here we report on our institutional experience with frameless robot-assisted stereotactic placement of intracerebral depth electrodes using the Neuromate® stereotactic robot-system. Methods: We identified all patients who had undergone robot-assisted stereotactic placement of intracerebral depth electrodes for invasive extra-operative epilepsy monitoring between September 2013 and March 2020. We studied technical (placement) and diagnostic accuracy of the robot-assisted procedure, associated surgical complications and procedural time requirements. Results: We evaluated a total of 464 depth electrodes implanted in 74 patients (mean 6 per patient, range 1–12). There were 27 children and 47 adults (age range: 3.6–64.6 yrs.). The mean entry and target point errors were 1.82±1.15 and 1.98±1.05 mm. Target and entry point errors were significantly higher in paediatric vs. adult patients and for electrodes targeting the temporo-mesial region. There were no clinically relevant haemorrhages and no infectious complications. Mean time for the placement of one electrode was 37±14 min and surgery time per electrode decreased with the number of electrodes placed. 55 patients (74.3%) underwent definitive surgical treatment. 36/51 (70.1%) patients followed for >12 months or until seizure recurrence became seizure-free (ILAE I). Conclusion: Frameless robot-guided stereotactic placement of depth electrodes with the Neuromate® stereotactic robot-system is safe and feasible even in very young children, with good in vivo accuracy and high diagnostic precision. The surgical workflow is time-efficient and further improves with increasing numbers of implanted electrodes.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Depth electrode; Epilepsy surgery; Invasive diagnostic; Robot; Stereotactic implantation

Surgical management of epilepsy due to cerebral cavernomas using neuronavigation and intraoperative MR imaging - Sommer, Bjoern; Kasper, Burkhard S.; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2013)
Objectives: Cure from seizures due to cavernomas might be surgically achieved dependent on both, the complete removal of the cavernoma as well as its surrounding hemosiderin rim. High field intraoperative MRI imaging (iopMRI) and neuronavigation might play a crucial role to achieve both goals. We retrospectively investigated the long-term results and impact of intraoperative 1.5T MRI (iopMRI) and neuronavigation on the completeness of surgical removal of a cavernous malformation (CM) and its perilesional hemosiderin rim as well as reduction of surgical morbidity. Methods: 26 patients (14 female, 12 male, mean age 39.1 years, range: 17-63 years) with CM related epilepsy were identified. Eighteen patients suffered from drug resistant epilepsy (69.2%). Mean duration of epilepsy was 11.9 years in subjects with drug resistant epilepsy (n = 18) and 0.3 years in subjects presenting with first-time seizures (n = 8). We performed 24 lesionectomies and two lesionectomies combined with extended temporal resections. Seven lesions were located extratemporally. Results: Complete CM removal was documented by postsurgical MRI in all patients. As direct consequence of iopMRI, refined surgery was necessary in 11.5% of patients to achieve complete cavernoma removal and in another 11.5% for complete resection of additional adjacent epileptogenic cortex. Removal of the hemosiderin rim was confirmed by iopMRI in 92% of patients. Two patients suffered from mild (7.7%) and one from moderate (3.8%) visual field deficits. Complete seizure control (Engel class 1A) was achieved in 80.8% of patients with a mean follow-up period of 47.7 months. Discussion: We report excellent long-term seizure control with minimal surgical morbidity after complete resection of CM using our multimodal approach. © W. S. Maney & Son Ltd 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cavernous hemangioma; Epilepsy outcome; Intraoperative high field MRI; Surgical morbidity

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Targeting TGFβ-activated kinase-1 activation in microglia reduces CAR T immune effector cell-associated neurotoxicity syndrome - Vinnakota, Janaki Manoja; Biavasco, Francesca; Schwabenland, Marius; Chhatbar, Chintan; Adams, Rachael C.; Erny, Daniel; Duquesne, Sandra; El Khawanky, Nadia; Schmidt, Dominik; Fetsch, Viktor; Zähringer, Alexander; Salié, Henrike; et al. (Nature Cancer, 2024)
Cancer immunotherapy with chimeric antigen receptor (CAR) T cells can cause immune effector cell-associated neurotoxicity syndrome (ICANS). However, the molecular mechanisms leading to ICANS are not well understood. Here we examined the role of microglia using mouse models and cohorts of individuals with ICANS. CD19-directed CAR (CAR19) T cell transfer in B cell lymphoma-bearing mice caused microglia activation and neurocognitive deficits. The TGFβ-activated kinase-1 (TAK1)–NF-κB–p38 MAPK pathway was activated in microglia after CAR19 T cell transfer. Pharmacological TAK1 inhibition or genetic Tak1 deletion in microglia using Cx3cr1CreER:Tak1fl/fl mice resulted in reduced microglia activation and improved neurocognitive activity. TAK1 inhibition allowed for potent CAR19-induced antilymphoma effects. Individuals with ICANS exhibited microglia activation in vivo when studied by translocator protein positron emission tomography, and imaging mass cytometry revealed a shift from resting to activated microglia. In summary, we prove a role for microglia in ICANS pathophysiology, identify the TAK1–NF-κB–p38 MAPK axis as a pathogenic signaling pathway and provide a rationale to test TAK1 inhibition in a clinical trial for ICANS prevention after CAR19 T cell-based cancer immunotherapy.
CRIS-Team Scopus Importer:2024-05-24

The course of tumor-related epilepsy in glioblastoma patients: A retrospective analysis - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Uhl, Martin; Brandner, Sebastian; Welte, Tamara; Schembs, Leah; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsy and Behavior, 2024)
Purpose: Many patients with glioblastoma suffer from tumor-related seizures. However, there is limited data on the characteristics of tumor-related epilepsy achieving seizure freedom. The aim of this study was to characterize the course of epilepsy in patients with glioblastoma and the factors that influence it. Methods: We retrospectively analyzed the medical records of glioblastoma patients treated at the University Hospital Erlangen between 01/2006 and 01/2020. Results: In the final cohort of patients with glioblastoma (n = 520), 292 patients (56.2 %) suffered from tumor-related epilepsy (persons with epilepsy, PWE). Levetiracetam was the most commonly used first-line antiseizure medication (n = 245, 83.9 % of PWE). The onset of epilepsy was preoperative in 154/292 patients (52.7 %). 136 PWE (46.6 %) experienced only one single seizure while 27/292 PWE (9.2 %) developed drug-resistant epilepsy. Status epilepticus occurred in 48/292 patients (16.4 %). Early postoperative onset (within 30 days of surgery) of epilepsy and total gross resection (compared with debulking) were independently associated with a lower risk of further seizures. We did not detect dose-dependent pro- or antiseizure effects of radiochemotherapy. Conclusion: Tumor-related epilepsy occurred in more than 50% of our cohort, but drug-resistant epilepsy developed in less than 10% of cases. Epilepsy usually started before tumor surgery.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Glioblastoma; Radiochemotherapy; Surgery; Tumor-related epilepsy

The current role of surgery for single brain metastases - Ersoy, Tunc Faik; Brainman, Daniel; Dimov, Diyan; Coras, Roland; Berger, Björn; Weissinger, Florian; Simon, Matthias (Brain and Spine, 2025)
Introduction: Surgery for singular brain metastases (BM) aims to improve survival by providing control of CNS disease. This concept may need to be refined against the background of recent advances in medical and radiation oncology. In particular there is a debate about the prognostic role of residual tumor. Research question: Does extent of resection influence overall- and cerebral progression-free-survival as well as functional outcome? Materials and methods: This retrospective series comprised 202 patients with single BM who underwent surgery 2015–2023. All patients underwent pre- and postoperative MR imaging. Results: Surgical indications included a tumor too large for radiosurgery (≥15.0 cm3; 42.5 %) and tissue acquisition for molecular analyses for potential therapeutic targets (21.8 %). Extent of resection was categorized as incomplete (8.4 %), questionably complete (22.3 %), and complete (69.3 %). Median residual tumor volume was only 0.12 cm3 (IQR 0.04–0.35). Complete resection was not correlated with better overall (OS) or CNS progression free survival. Complication rates and postoperative KPS did not vary significantly with resection category. Postoperative MRI revealed two cases with unilateral sigmoid sinus thrombosis in asymptomatic patients (cf. 11/16 [69.0 %] complications requiring treatment in symptomatic patients). We recorded 6.2 % major (CTCAE III-V) surgical, 5.3 % neurological, and 7.2 % medical complications. Postoperative treatment and major complications were prominent prognostic factors for OS. Conclusion: Small tumor remnants may have limited impact on survival. In the era of targeted therapies tissue acquisition for molecular analysis is an increasingly important indication for BM surgery.
CRIS-Team Scopus Importer:2025-09-19
Keywords: Functional outcome; MRI; Progression-free survival; Residual tumor; Single brain metastasis; Survival

The curse of in silico transformation from Palmini's into the ILAE classification system of focal cortical dysplasia: A critical comment - Blümcke, Ingmar; Coras, Roland (Epilepsia, 2013)
CRIS-Team Scopus Importer:2022-08-05

The genomic landscape across 474 surgically accessible epileptogenic human brain lesions - A López-Rivera, Javier; Leu, Costin; Macnee, Marie; Khoury, Jean; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Bhattarai, Nisha; Pérez-Palma, Eduardo; Hamer, Hajo; Brandner, Sebastian; Rössler, Karl; et al. (Brain, 2022)
Understanding the exact molecular mechanisms involved in the etiology of epileptogenic pathologies with or without tumor activity is essential for improving treatment of drug-resistant focal epilepsy. Here, we characterize the landscape of somatic genetic variants in resected brain specimens from 474 individuals with drug-resistant focal epilepsy using deep whole-exome sequencing (>350×) and whole-genome genotyping. Across the exome, we observe a greater number of somatic single-nucleotide variants (SNV) in low-grade epilepsy-associated tumors (LEAT; 7.92 ± 5.65 SNV) than in brain tissue from malformations of cortical development (MCD; 6.11 ± 4 SNV) or hippocampal sclerosis (HS; 5.1 ± 3.04 SNV). Tumor tissues also had the largest number of likely pathogenic variant carrying cells. LEAT had the highest proportion of samples with one or more somatic copy number variants (CNV; 24.7%), followed by MCD (5.4%) and HS (4.1%). Recurring somatic whole chromosome duplications affecting Chromosome 7 (16.8%), chromosome 5 (10.9%), and chromosome 20 (9.9%) were observed among LEAT. For germline variant-associated MCD genes such as TSC2, DEPDC5, and PTEN, germline SNV were frequently identified within large loss of heterozygosity regions, supporting the recently proposed ‘second hit’ disease mechanism in these genes. We detect somatic variants in twelve established lesional epilepsy genes and demonstrate exome-wide statistical support for three of these in the etiology of LEAT (e.g., BRAF) and MCD (e.g., SLC35A2 and MTOR). We also identify novel significant associations for PTPN11 with LEAT and NRAS Q61 mutated protein with a complex MCD characterized by polymicrogyria and nodular heterotopia. The variants identified in NRAS are known from cancer studies to lead to hyperactivation of NRAS, which can be targeted pharmacologically. We identify large recurrent 1q21-q44 duplication including AKT3 in association with focal cortical dysplasia type 2a with hyaline astrocytic inclusions, another rare and possibly under-recognized brain lesion. The clinical genetic analyses showed that the numbers of somatic SNV across the exome and the fraction of affected cells were positively correlated with the age at seizure onset and surgery in individuals with LEAT. In summary, our comprehensive genetic screen sheds light on the genome-scale landscape of genetic variants in epileptic brain lesions, informs the design of gene panels for clinical diagnostic screening, and guides future directions for clinical implementation of epilepsy surgery genetics.<br
Keywords: epilepsy; malformation of cortical development; low-grade epilepsy-associated tumor; hippocampal sclerosis; genetics

The ILAE consensus classification of focal cortical dysplasia: An update proposed by an ad hoc task force of the ILAE diagnostic methods commission - Najm, Imad; Lal, Dennis; Alonso Vanegas, Mario; Cendes, Fernando; Lopes-Cendes, Iscia; Palmini, Andre; Paglioli, Eliseu; Sarnat, Harvey B.; Walsh, Christopher A.; Wiebe, Samuel; Aronica, Eleonora; Baulac, Stephanie; et al. (Epilepsia, 2022)
Ongoing challenges in diagnosing focal cortical dysplasia (FCD) mandate continuous research and consensus agreement to improve disease definition and classification. An International League Against Epilepsy (ILAE) Task Force (TF) reviewed the FCD classification of 2011 to identify existing gaps and provide a timely update. The following methodology was applied to achieve this goal: a survey of published literature indexed with ((Focal Cortical Dysplasia) AND (epilepsy)) between 01/01/2012 and 06/30/2021 (n = 1349) in PubMed identified the knowledge gained since 2012 and new developments in the field. An online survey consulted the ILAE community about the current use of the FCD classification scheme with 367 people answering. The TF performed an iterative clinico-pathological and genetic agreement study to objectively measure the diagnostic gap in blood/brain samples from 22 patients suspicious for FCD and submitted to epilepsy surgery. The literature confirmed new molecular-genetic characterizations involving the mechanistic Target Of Rapamycin (mTOR) pathway in FCD type II (FCDII), and SLC35A2 in mild malformations of cortical development (mMCDs) with oligodendroglial hyperplasia (MOGHE). The electro-clinical-imaging phenotypes and surgical outcomes were better defined and validated for FCDII. Little new information was acquired on clinical, histopathological, or genetic characteristics of FCD type I (FCDI) and FCD type III (FCDIII). The survey identified mMCDs, FCDI, and genetic characterization as fields for improvement in an updated classification. Our iterative clinico-pathological and genetic agreement study confirmed the importance of immunohistochemical staining, neuroimaging, and genetic tests to improve the diagnostic yield. The TF proposes to include mMCDs, MOGHE, and “no definite FCD on histopathology” as new categories in the updated FCD classification. The histopathological classification can be further augmented by advanced neuroimaging and genetic studies to comprehensively diagnose FCD subtypes; these different levels should then be integrated into a multi-layered diagnostic scheme. This update may help to foster multidisciplinary efforts toward a better understanding of FCD and the development of novel targeted treatment options.
CRIS-Team Scopus Importer:2022-06-24
Keywords: brain; classification; epilepsy; focal cortical dysplasia; genes; seizure

The mFI-11 frailty index as a predictor of surgical outcomes in elderly patients with brain metastases - Quach, Stefanie; Coras, Roland; Weissinger, Florian; Simon, Matthias; Ersoy, Tunc Faik (Brain and Spine, 2026)
Introduction: The vulnerability towards disease but also treatment in elderly patients has been referred to as frailty and can be measured using frailty indices, which assess functional health and comorbidities. Frailty has been shown to correlate with survival and functional outcomes in brain tumor patients. Research question: Does frailty, assessed by the 11-item modified Frailty Index (mFI-11), provide useful prognostic information in elderly patients undergoing brain metastasis surgery? Material and methods: A retrospective analysis of 139 patients aged ≥60 years who underwent brain metastasis resection (2015–2019) was conducted. Frailty was assessed using the mFI-11. Results: Increasing frailty correlated with poorer median overall survival (mFI 0: 13.8 months [95 %-CI: 8.7–18.9] vs. mFI 1–2l: 8.7 [5.8–11.6] vs. mFI≥3: 2.8 [0.9–4.6], p = 0.001) and functional outcome (postoperative KPS 80–100 %, mFI 0: 27/36 [75.0 %] vs. mFI 1–2: 44/64 [68.8 %] vs. mFI≥3: 13/38 [34.2 %], p < 0.001). Age was less prognostic. In the multivariate analyses, mFI-11 and age were not independently predictive, while KPS was. Frailty was not associated with major complications. Discussion: While frailty correlates with outcome, functional health rather than comorbidities and age is prognostic. The mFI-11's predictive ability may be largely due to its inclusion of a functional health assessment. Conclusion: Functional health (KPS) is a much stronger predictor of survival and functional outcome in the elderly than the presence of comorbidities and age, i.e. age per se and comorbidities without impact on the patient's functional health status (i.e. well-treated) should not deter from surgery. Frailty is not a predictor of complications.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Brain metastases; Comorbidities; Elderly; Frailty; Functional outcome; Survival

The role of cytoreductive surgery in multifocal/multicentric glioblastomas - Dimov, Diyan; Brainman, Daniel; Berger, Björn; Coras, Roland; Grote, Alexander; Simon, Matthias (Journal of Neuro-Oncology, 2023)
Purpose: Multifocal/multicentric glioblastomas (mGBM) account for up to 20% of all newly diagnosed glioblastomas. The present study investigates the impact of cytoreductive surgery on survival and functional outcomes in patients with mGBM. Methods: We retrospectively reviewed clinical and imaging data of 71 patients with newly diagnosed primary (IDH1 wildtype) mGBM who underwent operative treatment in 2015–2020 at the authors’ institution. Multicentric/multifocal growth was defined by the presence of ≥ 2 contrast enhancing lesions ≥ 1 cm apart from each other. Results: 36 (50.7%) patients had a resection and 35 (49.3%) a biopsy procedure. MGMT status, age, preoperative KPI and NANO scores as well as the postoperative KPI and NANO scores did not differ significantly between resected and biopsied cases. Median overall survival was 6.4 months and varied significantly with the extent of resection (complete resection of contrast enhancing tumor: 13.6, STR: 6.4, biopsy: 3.4 months; P = 0.043). 21 (58.3%) of resected vs. only 12 (34.3%) of biopsied cases had radiochemotherapy (p = 0.022). Multivariate analysis revealed chemo- and radiotherapy and also (albeit with smaller hazard ratios) extent of resection (resection vs. biopsy) and multicentric growth as independent predictors of patient survival. Involvement of eleoquent brain regions, as well as neurodeficit rates and functional outcomes did not vary significantly between the biopsy and the resection cohorts. Conclusion: Resective surgery in mGBM is associated with better survival. This benefit seems to relate prominently to an increased number of patients being able to tolerate effective adjuvant therapies after tumor resections. In addition, cytoreductive surgery may have a survival impact per se.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Biopsy; Glioblastoma; Growth patterns; Multicentric; Multifocal; Resection

The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D - Wang, Dan-Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De-Hong; Coras, Roland; Wang, Yu-Jiao; Shi, Jie; Zhou, Wen-Jing; Kobow, Katja; Piao, Yue-Shan (Acta Neuropathologica Communications, 2023)
Focal Cortical Dysplasia (FCD) is a frequent cause of drug-resistant focal epilepsy in children and young adults. The international FCD classifications of 2011 and 2022 have identified several clinico-pathological subtypes, either occurring isolated, i.e., FCD ILAE Type 1 or 2, or in association with a principal cortical lesion, i.e., FCD Type 3. Here, we addressed the DNA methylation signature of a previously described new subtype of FCD 3D occurring in the occipital lobe of very young children and microscopically defined by neuronal cell loss in cortical layer 4. We studied the DNA methylation profile using 850 K BeadChip arrays in a retrospective cohort of 104 patients with FCD 1 A, 2 A, 2B, 3D, TLE without FCD, and 16 postmortem specimens without neurological disorders as controls, operated in China or Germany. DNA was extracted from formalin-fixed paraffin-embedded tissue blocks with microscopically confirmed lesions, and DNA methylation profiles were bioinformatically analyzed with a recently developed deep learning algorithm. Our results revealed a distinct position of FCD 3D in the DNA methylation map of common FCD subtypes, also different from non-FCD epilepsy surgery controls or non-epileptic postmortem controls. Within the FCD 3D cohort, the DNA methylation signature separated three histopathology subtypes, i.e., glial scarring around porencephalic cysts, loss of layer 4, and Rasmussen encephalitis. Differential methylation in FCD 3D with loss of layer 4 mapped explicitly to biological pathways related to neurodegeneration, biogenesis of the extracellular matrix (ECM) components, axon guidance, and regulation of the actin cytoskeleton. Our data suggest that DNA methylation signatures in cortical malformations are not only of diagnostic value but also phenotypically relevant, providing the molecular underpinnings of structural and histopathological features associated with epilepsy. Further studies will be necessary to confirm these results and clarify their functional relevance and epileptogenic potential in these difficult-to-treat children.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Epigenetic; Epilepsy; Malformation of cortical development; Neuropathology; Occipital lobe

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Toward a better definition of focal cortical dysplasia: An iterative histopathological and genetic agreement trial - Blümcke, Ingmar; Coras, Roland; Busch, Robyn M.; Morita-Sherman, Marcia; Lal, Dennis; Prayson, Richard; Cendes, Fernando; Lopes-Cendes, Iscia; Rogerio, Fabio; Almeida, Vanessa S.; Rocha, Cristiane S.; Sim, Nam Suk; et al. (Epilepsia, 2021)
Objective: Focal cortical dysplasia (FCD) is a major cause of difficult-to-treat epilepsy in children and young adults, and the diagnosis is currently based on microscopic review of surgical brain tissue using the International League Against Epilepsy classification scheme of 2011. We developed an iterative histopathological agreement trial with genetic testing to identify areas of diagnostic challenges in this widely used classification scheme. Methods: Four web-based digital pathology trials were completed by 20 neuropathologists from 15 countries using a consecutive series of 196 surgical tissue blocks obtained from 22 epilepsy patients at a single center. Five independent genetic laboratories performed screening or validation sequencing of FCD-relevant genes in paired brain and blood samples from the same 22 epilepsy patients. Results: Histopathology agreement based solely on hematoxylin and eosin stainings was low in Round 1, and gradually increased by adding a panel of immunostainings in Round 2 and the Delphi consensus method in Round 3. Interobserver agreement was good in Round 4 (kappa =.65), when the results of genetic tests were disclosed, namely, MTOR, AKT3, and SLC35A2 brain somatic mutations in five cases and germline mutations in DEPDC5 and NPRL3 in two cases. Significance: The diagnoses of FCD 1 and 3 subtypes remained most challenging and were often difficult to differentiate from a normal homotypic or heterotypic cortical architecture. Immunohistochemistry was helpful, however, to confirm the diagnosis of FCD or no lesion. We observed a genotype–phenotype association for brain somatic mutations in SLC35A2 in two cases with mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy. Our results suggest that the current FCD classification should recognize a panel of immunohistochemical stainings for a better histopathological workup and definition of FCD subtypes. We also propose adding the level of genetic findings to obtain a comprehensive, reliable, and integrative genotype–phenotype diagnosis in the near future.
CRIS-Team Scopus Importer:2021-05-14
Keywords: brain; classification; epilepsy; genes; neuropathology; seizure

Transcriptome analyses of the cortex and white matter of focal cortical dysplasia type II: Insights into pathophysiology and tissue characterization - Assis-Mendonça, Guilherme Rossi; Athié, Maria Carolina Pedro; Tamanini, João Vitor Gerdulli; Souza, Arethusa de; Zanetti, Gabriel Gerardini; Araújo, Patrícia Aline Oliveira Ribeiro de Aguiar; Ghizoni, Enrico; Tedeschi, Helder; Alvim, Marina Koutsodontis Machado; Almeida, Vanessa Simão de; de Souza, Welliton; Coras, Roland; et al. (Frontiers in Neurology, 2023)
Introduction: Focal cortical dysplasia (FCD) is a common cause of pharmacoresistant epilepsy. According to the 2022 International League Against Epilepsy classification, FCD type II is characterized by dysmorphic neurons (IIa and IIb) and may be associated with balloon cells (IIb). We present a multicentric study to evaluate the transcriptomes of the gray and white matters of surgical FCD type II specimens. We aimed to contribute to pathophysiology and tissue characterization. Methods: We investigated FCD II (a and b) and control samples by performing RNA-sequencing followed by immunohistochemical validation employing digital analyses. Results: We found 342 and 399 transcripts differentially expressed in the gray matter of IIa and IIb lesions compared to controls, respectively. Cholesterol biosynthesis was among the main enriched cellular pathways in both IIa and IIb gray matter. Particularly, the genes HMGCS1, HMGCR, and SQLE were upregulated in both type II groups. We also found 12 differentially expressed genes when comparing transcriptomes of IIa and IIb lesions. Only 1 transcript (MTRNR2L12) was significantly upregulated in FCD IIa. The white matter in IIa and IIb lesions showed 2 and 24 transcripts differentially expressed, respectively, compared to controls. No enriched cellular pathways were detected. GPNMB, not previously described in FCD samples, was upregulated in IIb compared to IIa and control groups. Upregulations of cholesterol biosynthesis enzymes and GPNMB genes in FCD groups were immunohistochemically validated. Such enzymes were mainly detected in both dysmorphic and normal neurons, whereas GPNMB was observed only in balloon cells. Discussion: Overall, our study contributed to identifying cortical enrichment of cholesterol biosynthesis in FCD type II, which may correspond to a neuroprotective response to seizures. Moreover, specific analyses in either the gray or the white matter revealed upregulations of MTRNR2L12 and GPNMB, which might be potential neuropathological biomarkers of a cortex chronically exposed to seizures and of balloon cells, respectively.
CRIS-Team Scopus Importer:2023-04-07
Keywords: cholesterol biosynthesis enzymes; focal cortical dysplasia; GPNMB; humanin-like 12; immunohistochemistry; molecular biomarker; transcriptome

Transdural Skull Base Infiltration by Glioblastoma: Case Report and Review of the Literature - Thrull, Michael; Atasi, Khaled; Boese, Lennart-Maximilian; Cakar, Mahmut; Heller, Ullrich; Jansen, Nils; Menzel, Leoni-Christine; Omaimen, Hassan; Theis, Katharina; Karacic, Damir; Dimov, Diyan; Coras, Roland; et al. (Case Reports in Otolaryngology, 2023)
We report the rare occurrence of a temporal glioblastoma multiforme (GBM) showing transdural tumor extension into adjacent mastoid cells. As the dura mater provides a barrier to intraaxial tumors, GBM seldom penetrates into the skull base, even though it is a high-grade astrocytoma with a tendency to spread. Yet, some mechanisms of GBM-induced skull invasion have been identified, making this entity a very rare but nonetheless relevant differential diagnosis in otherwise ambiguous cases of an intracerebral tumor extending into the skull base. In addition, imaging markers that may assist in distinguishing extra- from intraaxial tumor infiltration of the temporal bone are described.
CRIS-Team WoS Importer:2023-03-03

Validation of automatic MRI hippocampal subfield segmentation by histopathological evaluation in patients with temporal lobe epilepsy - Menzler, Katja; Hamer, Hajo; Mross, Peter; Rosenow, Felix; Deichmann, Ralf; Wagner, Marlies; Gracien, René Maxime; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Belke, Marcus; Knake, Susanne (Seizure-European Journal of Epilepsy, 2021)
Objective: The present study validates the results of automated hippocampal subfield segmentation with histopathology in epilepsy patients undergoing epilepsy surgery. Methods: We performed an automated hippocampal subfield segmentation on presurgical three-dimensional, T1-weighted magnetization Prepared Rapid Acquisition of Gradient Echoes Magnetic Resonance Imaging (MRI) data of 25 patients with unilateral mesial temporal lobe epilepsy due to hippocampal sclerosis (HS), using Freesurfer Version 6.0. The resulting volumes of cornu ammonis (CA) subfields CA1, CA2/3, CA4 and the dentate gyrus (DG) were compared to the histopathological cell count. Results: We found a significant correlation between histopathology in subregion CA2 and automated segmentation of subregion CA1 (p = 0.0062), CA2/3 (p = 0.004), CA4 (p = 0.0062) and the DG (p = 0.0054), between histopathology in CA3 and automated segmentation of CA1 (p = 0.0132), CA2/3 (p = 0.0004), CA4 (p = 0.0032) and the DG (p = 0.0037), as well as between histopathology in the DG and automated segmentation of CA1 (p = 0.0115), CA2/3 (p < 0.0001), CA4 (p < 0.0001) and the DG (p = 0.0001). The histopathological finding of HS type 1 could correctly be classified in all cases on MRI. Significance: The present study shows significant correlations between histopathological evaluation and results of the automated segmentation of the hippocampus, thereby validating the automated segmentation method. As the differential involvement of different hippocampal subfields may be associated with clinical parameters and the outcome after epilepsy surgery, the automated segmentation is also promising for prognostic purposes.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Automated segmentation; Hippocampal subfields; Mesiotemporal sclerosis; Mri

Value of 7T MRI and post-processing in patients with nonlesional 3T MRI undergoing epilepsy presurgical evaluation - Wang, Irene; Oh, Sehong; Blümcke, Ingmar; Coras, Roland; Krishnan, Balu; Kim, Sanghoon; Mcbride, Aaron; Grinenko, Olesya; Lin, Yicong; Overmyer, Margit; Aung, Tin Tun; Lowe, Mark; et al. (Epilepsia, 2020)
Objective: Ultra-high-field 7-Tesla (7T) magnetic resonance imaging (MRI) offers increased signal-to-noise and contrast-to-noise ratios, which may improve visualization of cortical malformations. We aim to assess the clinical value of in vivo structural 7T MRI and its post-processing for the noninvasive identification of epileptic brain lesions in patients with pharmacoresistant epilepsy and nonlesional 3T MRI who are undergoing presurgical evaluation. Methods: Sixty-seven patients were included who had nonlesional 3T MRI by official radiology report. Epilepsy protocols were used for the 3T and 7T acquisitions. Post-processing of the 7T T1-weighted magnetization-prepared two rapid acquisition gradient echoes sequence was performed using the morphometric analysis program (MAP) with comparison to a normal database consisting of 50 healthy controls. Review of 7T was performed by an experienced board-certified neuroradiologist and at the multimodal patient management conference. The clinical significance of 7T findings was assessed based on intracranial electroencephalography (ICEEG) ictal onset, surgery, postoperative seizure outcomes, and histopathology. Results: Unaided visual review of 7T detected previously unappreciated subtle lesions in 22% (15/67). When aided by 7T MAP, the total yield increased to 43% (29/67). The location of the 7T-identified lesion was identical to or contained within the ICEEG ictal onset in 13 of 16 (81%). Complete resection of the 7T-identified lesion was associated with seizure freedom (P =.03). Histopathology of the 7T-identified lesions encountered mainly focal cortical dysplasia (FCD). 7T MAP yielded 25% more lesions (6/24) than 3T MAP, and showed improved conspicuity in 46% (11/24). Significance: Our data suggest a major benefit of 7T with post-processing for detecting subtle FCD lesions for patients with pharmacoresistant epilepsy and nonlesional 3T MRI.
CRIS-Team Scopus Importer:2020-10-02
Keywords: 7T; focal cortical dysplasia; MRI; nonlesional; presurgical evaluation; ultra-high field

Variable histopathology features of neuronal dyslamination in the cerebral neocortex adjacent to epilepsy-associated vascular malformations suggest complex pathogenesis of focal cortical dysplasia ILAE type IIIc - Miyata, Hajime; Kuwashige, Haruka; Hori, Tomokatsu; Kubota, Yuichi; Pieper, Tom; Coras, Roland; Blümcke, Ingmar; Yoshida, Yasuji (Brain Pathology, 2022)
Focal cortical dysplasia type IIIc (FCD-IIIc) is histopathologically defined by the International League Against Epilepsy's classification scheme as abnormal cortical organization adjacent to epilepsy-associated vascular malformations (VM). However, the incidence of FCD-IIIc, its pathogenesis, or association with the epileptogenic condition remains to be clarified. We reviewed a retrospective series of surgical brain specimens from 14 epilepsy patients with leptomeningeal angiomatosis of Sturge-Weber syndrome (LMA-SWS; n = 6), cerebral cavernous malformations (CCM; n = 7), and an arteriovenous malformation (AVM; n = 1) to assess the histopathological spectrum of FCD-IIIc patterns in VM. FCD-IIIc was observed in all cases of LMA-SWS and was designated as cortical pseudolaminar sclerosis (CPLS). CPLS showed a common pattern of horizontally organized layer abnormalities, including neuronal cell loss and astrogliosis, either manifesting predominantly in cortical layer (L) 3 extending variably to deeper areas with or without further extension to L2 and/or L4. Another pattern was more localized, targeting mainly L4 with extension to L3 and/or L5. Abnormal cortical layering characterized by a fusion of L2 and L3 or L4–L6 was also noted in two LMA-SWS cases and the AVM case. No horizontal or vertical lamination abnormalities were observed in the specimens adjacent to the CCM, despite the presence of vascular congestion and dilated parenchymal veins in all VM. These findings suggest that FCD-IIIc depends on the type of the VM and developmental timing. We further conclude that FCD-IIIc represents a secondary lesion acquired during pre- and/or perinatal development rather than following a pathomechanism independent of LMA-SWS. Further studies will be necessary to address the selective vulnerability of the developing cerebral neocortex in LMA-SWS, including genetic, encephaloclastic, hemodynamic, or metabolic events.
CRIS-Team Scopus Importer:2022-01-21

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic